Quantum dot-containing composition, and quantum dot-containing member, backlight device, display device, and liquid crystal display element using said quantum dot-containing composition

A quantum dot-containing composition with specific ratios of polyfunctional (meth)acrylate and thiol, along with a reaction retardant, forms a durable quantum dot member, addressing durability issues and enabling mass production without barrier layers, enhancing display device performance.

JP7604811B2Active Publication Date: 2024-12-24TOPPAN HOLDINGS INC
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2020148656
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-05-15
Filing Date
2020-09-04
Publication Date
2024-12-24
Estimated Expiration
2040-09-04

AI Technical Summary

Technical Problem

Existing quantum dot compositions are prone to deterioration due to heat, water, and oxygen, leading to reduced optical properties and poor durability, especially when used in display devices without barrier layers.

Method used

A quantum dot-containing composition comprising polyfunctional (meth)acrylate, polyfunctional thiol, reaction retardant, quantum dots, and optional scattering agent, with specific mole ratios and concentrations, is used to form a durable quantum dot-containing member without barrier layers, enhancing durability and mass production suitability.

Benefits of technology

The composition achieves excellent durability and color reproducibility in display devices, allowing for mass production and extended lifespan without the need for barrier layers, thereby improving display quality and longevity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604811000006
    Figure 0007604811000006
  • Figure 0007604811000007
    Figure 0007604811000007
  • Figure 0007604811000008
    Figure 0007604811000008
Patent Text Reader

Abstract

To provide a quantum dot-containing composition which, especially, has a superior pot life, and contains quantum dots suitable to mass-production, and a quantum dot-containing member, a backlight device, display device, and a liquid crystal display element that use the quantum dot-containing composition to have superior temporal durability.SOLUTION: A quantum dot-containing composition includes multifunctional (meth)acrylate, multifunctional thiol, a reaction retarder, and quantum dots. In the present invention, a ratio of a mol number of a (meth)acrylate group of the multifunctional (meth)acrylate and a mole number of a mercapto group of the multifunctional thiol is preferably 0.6-9.0. The quantum dot-containing member is formed by curing the quantum dot-containing composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a quantum dot-containing composition that contains quantum dots, and a quantum dot-containing member, a backlight device, a display device, and a liquid crystal display element that use the quantum dot-containing composition. [Background technology]

[0002] In recent years, in the field of image display devices such as liquid crystal displays and smartphones, there is a strong demand for improving color reproducibility in order to obtain higher definition images. As one of the means for improving color reproducibility, for example, as shown in the following Patent Documents 1 and 2, materials using quantum dots have been actively developed.

[0003] Patent document 2 discloses a method for obtaining white light by using blue LED light to excite quantum dots that emit red and green light, and by using the white light obtained in this way, it is possible to significantly improve color reproducibility compared to the case where a conventional white LED is used.

[0004] However, quantum dots are vulnerable to heat, water, light, oxygen, etc., and the luminescence properties of quantum dots deteriorate over time, with the deterioration being particularly rapid in the presence of water and oxygen.

[0005] To solve this problem, for example, Patent Document 2 discloses a method for preventing the quantum dots from being exposed to water and oxygen by curing a resin composition containing quantum dots to produce a resin film containing quantum dots (hereinafter referred to as a quantum dot film), and then sandwiching the film between barrier films having an airtight layer formed on the surface by a method such as coating or vapor deposition.

[0006] However, the method disclosed in Patent Document 2 has the problem that the coloring by the airtight layer deteriorates the optical properties, and the airtight layer is partially damaged during the production of the laminated film, which deteriorates the optical properties due to partial deterioration of the airtightness. In addition, the end of the laminated film has lower airtightness than the center of the laminated film, so there is a problem that fading occurs from the end of the quantum dot film toward the inside over time.

[0007] Furthermore, Patent Document 3 discloses a method for preventing the quantum dots from being exposed to water and oxygen by dispersing and curing quantum dots in a resin composition containing a (meth)allyl compound, a (meth)acrylic compound, a photopolymerization initiator, and a thioether oligomer to produce a quantum dot film, and then sandwiching the quantum dots between barrier films in the same manner as in Patent Document 2 to produce a laminated film.

[0008] However, the method disclosed in Patent Document 3 has difficulty in solving the same problems as those in Patent Document 2. In addition, since (meth)allyl compounds have lower reactivity than (meth)acrylic compounds, there is a problem that the amount of unreacted (meth)allyl compounds increases, resulting in deterioration of durability.

[0009] Furthermore, the invention described in Patent Document 4 is based on the premise that a barrier layer is provided on both sides of the quantum dot layer, and does not describe a quantum dot-containing member that has excellent durability without using a barrier layer. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Special Publication No. 2016-511709 [Patent Document 2] Patent No. 5940079 [Patent Document 3] International Publication No. 2018 / 056469 [Patent Document 4] Korean Patent No. 10-1969561 [Patent Document 5] JP 2017-032918 A [Patent Document 6] JP 2019-086555 A [Patent Document 7] JP 2018-124412 A [Patent Document 8] JP 2017-214486 A Summary of the Invention [Problem to be solved by the invention]

[0011] The present invention has been made in consideration of the above-mentioned current situation, and has an object to provide a quantum dot-containing composition containing quantum dots that has an excellent pot life and is suitable for mass production, and a quantum dot-containing member, a backlight device, a display device, and a liquid crystal display element that are excellent in durability over time by using the quantum dot-containing composition. [Means for solving the problem]

[0012] The quantum dot-containing composition of the present invention comprises a multifunctional (meth)acrylate, a multifunctional thiol, a reaction retarder, quantum dots, a scattering agent, and a photopolymerization initiator, and is characterized in that the ratio of the number of moles of (meth)acrylate groups in the multifunctional (meth)acrylate to the number of moles of mercapto groups in the multifunctional thiol is in the range of 1.0 or more and 2.5 or less. The quantum dot-containing composition of the present invention comprises a multifunctional (meth)acrylate, a multifunctional thiol, a reaction retarder, quantum dots, a scattering agent, and a photopolymerization initiator, and is characterized in that the reaction retarder is contained in an amount of 0.0005% by mass or more and 0.5% by mass or less relative to 100% by mass of the sum of the multifunctional (meth)acrylate and the multifunctional thiol. 。

[0013] In the present invention, the ratio of the number of moles of the (meth)acrylate groups in the polyfunctional (meth)acrylate to the number of moles of the mercapto groups in the polyfunctional thiol is preferably in the range of 0.6 or more and 9.0 or less. In the present invention, the reaction retarder is preferably at least one selected from a phosphorous acid compound and a dithiocarbamate compound.

[0014] In the present invention, the reaction retarder is preferably contained in an amount of 0.0005% by mass or more and 1% by mass or less relative to 100% by mass of the sum of the polyfunctional (meth)acrylate and the polyfunctional thiol.

[0015] The quantum dot-containing composition of the present invention comprises a polyfunctional (meth)acrylate, a polyfunctional thiol, a reaction retarder, and quantum dots, and is characterized in that the reaction retarder comprises a dithiocarbamate compound.

[0016] In the present invention, it is preferable that the composition further contains a scattering agent and a photopolymerization initiator.

[0017] In the present invention, it is preferable that the scattering agent contains fine particles having at least one of a melamine structure and a benzoguanamine structure.

[0018] In the present invention, it is preferable that the composition further contains a dispersing resin, the dispersing resin being at least one selected from an acrylic resin, a polyurethane resin, a polyester resin, and a polyethyleneimine resin, and the functional group of the dispersing resin being at least one selected from a phosphate group, an amino group, and a mercapto group.

[0019] In the present invention, the dispersion resin is preferably contained in an amount of 0.1% by mass or more and 5% by mass or less with respect to 100% by mass of the sum of the polyfunctional (meth)acrylate and the polyfunctional thiol.

[0020] The quantum dot-containing composition of the present invention comprises a multifunctional (meth)acrylate, a multifunctional thiol, a reaction retarder, a scattering agent, a photopolymerization initiator, and quantum dots, and is characterized in that the ratio of the number of moles of (meth)acrylate groups in the multifunctional (meth)acrylate to the number of moles of mercapto groups in the multifunctional thiol is in the range of 0.8 or more and 5.5 or less.

[0021] In the present invention, the ratio of the number of moles of the (meth)acrylate groups in the polyfunctional (meth)acrylate to the number of moles of the mercapto groups in the polyfunctional thiol is preferably in the range of 1.52 or more and 9.0 or less.

[0022] The quantum dot-containing member of the present invention is characterized by being obtained by curing the quantum dot-containing composition described above.

[0023] In the present invention, the composition preferably comprises a quantum dot layer formed by curing the quantum dot-containing composition, and a base film covering at least one surface of the quantum dot layer.

[0024] In the present invention, it is preferable to have a quantum dot layer obtained by curing the quantum dot-containing composition, a base film covering one side of the quantum dot layer, and an optical member in contact with a side of the quantum dot layer opposite to the base film.

[0025] In the present invention, the optical member is preferably a light guide plate or a diffusion plate.

[0026] In the present invention, it is preferable that no barrier layer is disposed on the surface of the quantum dot-containing member.

[0027] The backlight device of the present invention is characterized by comprising the quantum dot-containing member described above.

[0028] A display device according to the present invention is characterized by comprising the quantum dot-containing member described above.

[0029] The liquid crystal display element of the present invention is characterized in that the above-described quantum dot-containing member is incorporated into a backlight device. Effect of the Invention

[0030] By using the quantum dot-containing composition of the present invention, it is possible to mass-produce, for example, quantum dot-containing members containing quantum dots, which have excellent durability without using a barrier layer, thereby contributing to the spread of display members and the like having excellent color reproducibility. [Brief description of the drawings]

[0031] [Figure 1A] FIG. 1 is a schematic diagram of a quantum dot. [Figure 1B] FIG. 1 is a schematic diagram of a quantum dot. [Diagram 2] 1 is a longitudinal sectional view of a quantum dot-containing member showing a first embodiment of the present invention. [Diagram 3] FIG. 2 is a longitudinal sectional view of a quantum dot-containing member showing a second embodiment of the present invention. [Figure 4] FIG. 11 is a longitudinal sectional view of a quantum dot-containing member showing a third embodiment of the present invention. [Diagram 5] FIG. 2 is a perspective view of the quantum dot-containing member of the present embodiment. [Figure 6] 1 is a longitudinal sectional view of a display device using a quantum dot-containing member according to an embodiment of the present invention. [Figure 7] 7 is a vertical cross-sectional view of a display device using a quantum dot-containing member according to the present embodiment, different from that shown in FIG. 6. [Figure 8] 1 is a longitudinal sectional view of a light-guiding member using a quantum dot-containing member according to an embodiment of the present invention. [Figure 9] 1 is a longitudinal sectional view of a liquid crystal display element using a quantum dot-containing member according to an embodiment of the present invention. [Figure 10] 1 is a longitudinal sectional view of a liquid crystal display element using a quantum dot-containing member according to an embodiment of the present invention. [Figure 11] 1 is a longitudinal sectional view of a liquid crystal display element using a quantum dot-containing member according to an embodiment of the present invention. [Figure 12] 1 is a cross-sectional view showing an example of a quantum dot-containing member according to an embodiment of the present invention. [Figure 13] 1A to 1C are cross-sectional views showing an example of the production of a quantum dot-containing member according to the present embodiment. [Figure 14A] FIG. 2 is a cross-sectional view of a quantum dot-containing member having substrate films on both sides of a quantum dot layer. [Figure 14B] 14B is a cross-sectional view of the quantum dot-containing member in which one side of the base film shown in FIG. 14A is peeled off, leaving the base film only on one side of the quantum dot layer. [Figure 15] 1 is a conceptual diagram showing a manufacturing apparatus for manufacturing a quantum dot-containing member according to an embodiment of the present invention. [Figure 16] 1 is a graph showing the relationship between wavelength (400 nm to 700 nm) and brightness when using a quantum dot-containing direct-type optical element equipped with a partially reflective sheet and a quantum dot-containing direct-type optical element without a partially reflective sheet. [Figure 17] 1 is a graph showing the relationship between wavelength (400 nm to 700 nm) and brightness using a quantum dot-containing direct-type optical element (with DBEF) equipped with a partially reflective sheet and a quantum dot-containing direct-type optical element (with DBEF) without a partially reflective sheet. [Figure 18] 1 is a graph showing the relationship between wavelength (500 nm to 700 nm) and brightness when using a quantum dot-containing direct-type optical element equipped with a partially reflective sheet and a quantum dot-containing direct-type optical element without a partially reflective sheet. [Figure 19] This is a graph showing the relationship between wavelength (500nm to 700nm) and brightness using a quantum dot-containing direct-type optical element (with DBEF) equipped with a partially reflective sheet and a quantum dot-containing direct-type optical element (with DBEF) without a partially reflective sheet. [Figure 20] 1 is a graph showing the relationship between wavelength (400 nm to 700 nm) and brightness when using a quantum dot-containing edge type optical element equipped with a partially reflective sheet and a quantum dot-containing edge type optical element without a partially reflective sheet. [Figure 21]1 is a graph showing the relationship between wavelength (400 nm to 700 nm) and brightness using a quantum dot-containing edge-type optical element (with DBEF) equipped with a partially reflective sheet and a quantum dot-containing edge-type optical element (with DBEF) without a partially reflective sheet. [Figure 22] 1 is a graph showing the relationship between wavelength (500 nm to 700 nm) and brightness when using a quantum dot-containing edge type optical element equipped with a partially reflective sheet and a quantum dot-containing edge type optical element without a partially reflective sheet. [Figure 23] 1 is a graph showing the relationship between wavelength (500 nm to 700 nm) and brightness using a quantum dot-containing edge-type optical element (with DBEF) equipped with a partially reflective sheet and a quantum dot-containing edge-type optical element (with DBEF) without a partially reflective sheet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] The following describes the embodiments of the present invention in detail, but the following description is an example (representative example) of the embodiments of the present description, and the present invention is not limited to these contents as long as it does not deviate from the gist of the present invention. In addition, the notation "~" used below includes both the lower limit and the upper limit within the range.

[0033] The present inventors have developed a quantum dot-containing composition capable of improving durability without using (meth)allyl, for example, as shown in Patent Document 3. That is, in this embodiment, when including (meth)acrylate and thiol, a multifunctional (meth)acrylate and a multifunctional thiol are used. A sufficient degree of crosslinking can be obtained compared to a monofunctional one, and excellent durability can be obtained. On the other hand, the use of a multifunctional (meth)acrylate and a multifunctional thiol makes the reaction very fast. Therefore, a reaction retarder is added to delay the reaction and obtain an excellent pot life.

[0034] As described above, the quantum dot-containing composition in the present embodiment is characterized by including a multifunctional (meth)acrylate, a multifunctional thiol, a reaction retarder, and quantum dots. This allows the quantum dot-containing member formed using the quantum dot-containing composition to have excellent durability without arranging a barrier layer. Each substance contained in the quantum dot-containing composition will be described below.

[0035] <Polyfunctional (meth)acrylate (A)> The polyfunctional (meth)acrylate has two or more (meth)acrylate groups in one molecule. In this embodiment, a cured film can be obtained by radically polymerizing the polyfunctional (meth)acrylate and the polyfunctional thiol (B) described below using a photopolymerization initiator (F) described below. This cured film can dramatically improve the durability of the quantum dots (D) described below. In addition, it also functions as an adhesive for bonding two plastic films together when producing a quantum dot-containing member (e.g., a laminated film) described below.

[0036] The polyfunctional monomer used in the present embodiment is not limited to the following, but examples thereof include 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, tetrapropylene glycol diacrylate, polypropylene glycol diacrylate, neopentyl glycol diacrylate, neopentyl glycol PO-modified diacrylate, hydroxypivalic acid neopentyl glycol ester diacrylate, caprolactone adduct diacrylate of hydroxypivalic acid neopentyl glycol ester, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, tetrapropylene glycol diacrylate, polypropylene glycol diacrylate, neopentyl glycol diacrylate, hydroxypivalic acid neopentyl glycol ester ... ,6-hexanediol bis(2-hydroxy-3-acryloyloxypropyl)ether, bis(4-acryloxypolyethoxyphenyl)propane, 1,9-nonanediol diacrylate, pentaerythritol diacrylate, pentaerythritol diacrylate monostearate, pentaerythritol diacrylate monobenzoate, bisphenol A diacrylate, EO modified bisphenol A diacrylate, PO modified bisphenol A diacrylate, bisphenol F diacrylate, EO modified bisphenol F diacrylate, PO modified bisphenol F diacrylate, EO modified tetrabromobisphenol A diacrylate, tricyclodecane dimethylol diacrylate, isocyanuric acid EO modified diacrylate, 2-hydroxy-1,3-diacryloxypropane and other bifunctional acrylate monomers; trifunctional acrylate monomers such as glycerin PO-modified triacrylate, trimethylolpropane triacrylate, trimethylolpropane EO-modified triacrylate, trimethylolpropane PO-modified triacrylate, isocyanuric acid EO-modified triacrylate, isocyanic acid EO-modified ε-caprolactone-modified triacrylate, 1,3,5-triacryloylhexahydro-s-triazine, pentaerythritol triacrylate, and dipentaerythritol triacrylate tripropionate; Examples of the acrylate monomer include tetrafunctional or higher acrylate monomers such as pentaerythritol tetraacrylate, dipentaerythritol tetraacrylate, dipentaerythritol pentaacrylate monopropionate, dipentaerythritol hexaacrylate, tetramethylolmethane tetraacrylate, oligoester tetraacrylate, and tris(acryloyloxy)phosphate. These may be used alone or in any combination of two or more.

[0037] The average number of functional groups per molecule of the polyfunctional (meth)acrylate (A) used in the present embodiment is preferably 2 or more, more preferably 2.5 or more, and even more preferably 3 or more. When the number of functional groups is 2 or more, a sufficient degree of crosslinking can be obtained as a cured film, and excellent durability can be obtained.

[0038] <Multifunctional thiol (B)> The polyfunctional thiol (B) used in the present embodiment has two or more mercapto groups in one molecule. The polyfunctional thiol (B) is used to impart excellent oxygen barrier properties to a cured film with the polyfunctional (meth)acrylate (A).

[0039] The polyfunctional thiol (B) used in the present embodiment is not limited to the following, but may be, for example, ethylene glycol bis(3-mercaptopropionate), diethylene glycol bis(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptopropionate), 1,2-propylene glycol bis(3-mercaptopropionate), diethylene glycol bis(3-mercaptobutyrate), 1,4-butanediol bis(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptopropionate), 1,2-propylene glycol bis(3-mercaptopropionate), diethylene glycol bis(3-mercaptobutyrate), tetraethylene glycol bis(3-mercaptopropionate ... bis(3-mercaptopropionate), 1,4-butanediol bis(3-mercaptobutyrate), 1,8-octanediol bis(3-mercaptopropionate), 1,8-octanediol bis(3-mercaptobutyrate), hexanediol bisthioglycolate, trimethylolpropane tris(3-mercaptopropionate), trimethylolpropane tris(3-mercaptobutyrate), trimethylolpropane tris(3-mercaptopropionate), butyrate), trimethylolpropane tris(thioglycolate), tris-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, trimethylolethane tris(3-mercaptobutyrate), pentaerythritol tetrakis(3-mercaptopropionate), pentaerythritol Examples of such compounds include tetrakis(3-mercaptobutyrate), pentaerythritol tetrakis(3-mercaptoisobutyrate), dipentaerythritol hexakis(3-mercaptopropionate), dipentaerythritol hexa-cis(3-mercaptobutyrate), dipentaerythritol hexa-cis(3-mercaptoisobutyrate), pentaerythritol tetrakisthioglycolate, dipentaerythritol hexa-cisthioglycolate, etc. These compounds may be used alone or in any combination of two or more.

[0040] The average number of functional groups per molecule of the polyfunctional thiol (B) used in the present embodiment is preferably 2 or more, more preferably 2.5 or more, and even more preferably 3 or more. By having the number of functional groups of 2 or more, a sufficient degree of crosslinking can be obtained as a cured film, and excellent durability can be obtained.

[0041] The ratio of the number of moles of the (meth)acrylate group of the polyfunctional (meth)acrylate (A) to the number of moles of the mercapto group of the polyfunctional thiol (B) used in this embodiment (number of moles of acrylate group / number of moles of mercapto group) is preferably in the range of 0.6 to 9.0, more preferably in the range of 0.8 to 5.5, and even more preferably in the range of 1.0 to 2.5. When the molar ratio of the mercapto group to the (meth)acrylate group is in the range of 0.6 to 9.0, preferably in the range of 0.8 to 5.5, a film with high crosslink density is formed after the curing reaction, and excellent durability is obtained. Alternatively, the ratio of the number of moles of the (meth)acrylate group of the polyfunctional (meth)acrylate (A) to the number of moles of the mercapto group of the polyfunctional thiol (B) used in this embodiment (number of moles of acrylate group / number of moles of mercapto group) is preferably in the range of 1.52 to 9.0.

[0042] <Reaction retarder (C)> The reaction retarder (C) used in the present embodiment is added to delay the reaction between the (meth)acrylate group and the mercapto group when the multifunctional (meth)acrylate and the multifunctional thiol are mixed, thereby obtaining an excellent pot life.

[0043] Examples of the reaction retarder (C) used in this embodiment include, but are not limited to, phenolic compounds, phosphorous compounds, dithiocarbamate compounds, etc. Among them, from the viewpoint that an excellent pot life can be obtained with a small amount of compounding, it is preferable to select at least one of phosphorous compounds and dithiocarbamate compounds. Examples of phenolic compounds include, but are not limited to, 4-methoxyphenol, hydroquinone, etc. Examples of phosphorous compounds include, but are not limited to, dimethyl phosphite, diethyl phosphite, dibutyl phosphite, diisopropyl phosphite, diisobutyl phosphite, diphenyl phosphite, dibenzyl phosphite, bis(2,2,2-trifluoroethyl) phosphite, trimethyl phosphite, triethyl phosphite, triisopropyl phosphite, tributyl phosphite, trihexyl phosphite, triethylhexyl phosphite, trioctyl phosphite, triisodecyl phosphite, trilauryl phosphite, triphenyl phosphite, tri-o-tolyl phosphite, etc. Examples of dithiocarbamate compounds include, but are not limited to, tetramethylthiuram disulfide, tetraethylthiuram disulfide, tetraisopropylthiuram disulfide, tetrabutylthiuram disulfide, tetramethylthiuram monosulfide, dipentamethylenethiuram tetrasulfide, etc. These may be used alone or in any combination of two or more.

[0044] In this embodiment, it is more preferable to use a dithiocarbamate compound as the reaction retarder.

[0045] The amount of the reaction retarder (C) used in this embodiment is preferably 0.0005% by mass or more and 1% by mass or less, more preferably 0.0005% by mass or more and 0.5% by mass or less, based on the sum of the polyfunctional (meth)acrylate (A) and the polyfunctional thiol (B) (100% by mass). When the amount is 0.0005% by mass or more, a sufficient reaction retardation effect is obtained and a good pot life is obtained. Also, when the amount is 0.5% by mass or less, curing inhibition during the curing reaction process during the preparation of the quantum dot-containing member can be suppressed, and excellent durability can be obtained.

[0046] <Quantum dots (D)> The quantum dots (D) used in this embodiment are nanoparticles having a particle size of several nm to several tens of nm, and are materials that absorb excitation light and emit light efficiently. The peak wavelength of emission can be controlled by the composition and particle size of the nanoparticles, and quantum dots that emit red and green light are preferably used for display material applications. In some cases, quantum dots that emit blue light may be used, and quantum dots with a suitable wavelength can be used in this embodiment as well.

[0047] The quantum dots (D) used in the present embodiment include, but are not limited to, II-VI group semiconductors such as CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, Zn0, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZeSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe; GaN, GaP, GaAs, GaSb, AlN, AlP, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AINP, AINAs, AINSb, AIPAs, AIPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAINP, III-V semiconductors such as GaAINAs, GaAINSb, GaAIPAs, GaAIPSb, GaAINAs, GaAINSb, GaAIPAs, GaAIPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAINP, InAINAs, InAINSb, InAIPAs, InAIPSb; IV-VI semiconductors such as SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe; Group IV semiconductors such as Si, Ge, SiC, and SiGe; Alternatively, semiconductors doped with a metal element such as Mn may be used. These may be used alone or in any combination of two or more.

[0048] Fig. 1A is a schematic diagram of a quantum dot 5. As shown in Fig. 1A, in order to suppress aggregation of the quantum dots 5 used in this embodiment and to obtain excellent optical properties, it is preferable that a large number of organic ligands 6 are coordinated to the surface of the quantum dots 5.

[0049] The ligand used in the present embodiment is not limited to the following, but may be, for example, oleylamine: 18 H 35 NH 2 , Stearyl (octadecyl)amine: C 18 H 37 NH 2 , dodecyl(lauryl)amine: C 12 H 25 NH 2 , Decylamine: C 10 H 21 NH2 , Octylamine: C 8 H 17 NH 2 Aliphatic amine compounds such as; Fatty acids, oleic acid: C 17 H 33 COOH, stearic acid: C 17 H 35 COOH, Palmitic acid: C 15 H 31 COOH, myristic acid: C 13 H 27 COOH, lauryl(dodecanoic) acid: C 11 H 23 COOH, decanoic acid: C 9 H 19 COOH, octanoic acid: C 7 H 15 Fatty acid compounds such as COOH; Octadecanethiol: C 18 H 37 SH, hexanedecanethiol: C 16 H 33 SH, tetradecanethiol: C 14 H 29 SH, dodecanethiol: C 12 H 25 SH, decanethiol: C 10 H 21 SH, Octanethiol: C 8 H 17 Thiol compounds such as SH; Trioctylphosphine: (C 8 H 17 ) 3 P, triphenylphosphine: (C 6 H 5 ) 3 P, tributylphosphine: (C 4 H 9 ) 3 P Phosphine oxide series, trioctylphosphine oxide: (C 8 H 17 ) 3 P=O, triphenylphosphine oxide: (C 6 H 5 ) 3 P=O, tributylphosphine oxide: (C4 H 9 ) 3 Examples include phosphine-based compounds such as P=O. These may be used alone or in any combination of two or more.

[0050] As shown in FIG. 1B, the quantum dots 5 used in the present embodiment preferably have a core-shell structure consisting of a core portion 5a and a shell portion 5b, from the viewpoint of high quantum efficiency of light emission and excellent stability to light, oxygen, etc. Combinations of materials for the core-shell structure are not limited to the following, but include, for example, CdS / ZnS, CdSe / ZnS, CdSeS / ZnSe, InP / ZnS, PbSe / PbS, CdTe / ZnS, ZnCdSe / ZnS, ZnCeTe / ZnS, ZnSe / ZnS, ZnTe / ZnS, AgInGaS / ZnS, AgInS / ZnS, etc., and the shell portion 5b may have a multi-layer structure, such as CdS / ZnSeS / ZnS, CdSe / ZnSeS / ZnS, etc. The quantum dots 5 may be composed of only one of these, or two or more of them may be used in any combination. In Fig. 1B, the boundary between the core portion 5a and the shell portion 5b is shown by a dotted line, but this means that the boundary between the core portion 5a and the shell portion 5b does not have to be clearly confirmed by analysis. Also, the shell portion 5b may be in a state of being solid-solubilized on the surface of the core portion 5a.

[0051] As the quantum dots (D) used in this embodiment, quantum dots that emit green light having a peak wavelength of 520 to 560 nm (hereinafter referred to as green quantum dots) and quantum dots that emit red light having a peak wavelength of 600 to 680 nm (hereinafter referred to as red quantum dots) are preferably used. On the other hand, blue light having a peak wavelength of 430 nm to 480 nm is irradiated as excitation light, and the green quantum dots and red quantum dots that absorb this emit green and red light, and further, white light can be obtained by combining the blue light that is not absorbed and transmitted. In addition, in order to balance the intensities of the blue light, green light, and red light, quantum dots that emit blue light having a peak wavelength of 430 nm to 480 nm may be used. In addition, quantum dots with a fluorescence half width (Full Width at Half Maximum: FWHM) of 30 nm or less, preferably 25 nm or less, more preferably 20 nm or less are preferably used.

[0052] The amount of the quantum dots (D) used in this embodiment is preferably in the range of 0.03% by mass to 2% by mass, more preferably 0.05% by mass to 1% by mass, based on the sum of the multifunctional (meth)acrylate (A) and the multifunctional thiol (B) (100% by mass). In this way, when the amount of the quantum dots (D) is in the range of 0.03 to 2% by mass, sufficient luminescence intensity derived from the quantum dots can be obtained.

[0053] <Scattering agent (E)> In this embodiment, a scattering agent (E) can be further included. The scattering agent (E) used in this embodiment can scatter the excitation light of the quantum dots (D), thereby extending the optical path length, and as a result, the emission intensity of the quantum dots can be efficiently increased.

[0054] Examples of the scattering agent (E) used in this embodiment include organic scattering agents, inorganic scattering agents, and organic-inorganic hybrid scattering agents. Examples of the organic scattering agents used in this embodiment include, but are not limited to, resin fine particles such as polystyrene-based fine particles, polymethyl methacrylate-based fine particles, polyurethane-based fine particles, polyethylene-based fine particles, polypropylene-based fine particles, melamine-based fine particles, and benzoguanamine-based fine particles. These may be used alone or in any combination of two or more. In addition, these are generally obtained by heterogeneous polymerization such as suspension polymerization, and may be those that are crosslinked inside the particles or have functional groups such as acrylate groups on the surface.

[0055] The inorganic scattering agent used in the present embodiment includes, but is not limited to, silica particles such as colloidal silica, fumed silica, and precipitated silica, inorganic oxides such as alumina particles, zirconia particles, titania particles, and zinc oxide particles, talc, mica, kaolin, and clay. These may be used alone or in any combination of two or more. In addition, these may be surface-treated with a silane coupling agent or the like.

[0056] The organic-inorganic hybrid used in the present embodiment includes, but is not limited to, fine silica particle-containing resin particles, fine titania particle-containing resin particles, silica-modified resin particles, etc. These may be used alone or in any combination of two or more kinds.

[0057] The scattering agent (E) used in this embodiment is preferably fine particles having at least one of a melamine and a benzoguanamine structure, from the viewpoint that a high refractive index results in high scattering efficiency, and a high transparency results in high quantum yield.

[0058] The amount of the scattering agent (E) used in this embodiment is preferably in the range of 0.05% by mass or more and 10% by mass or less, and more preferably in the range of 0.1% by mass or more and 8% by mass or less, relative to 100% by mass of the sum of the polyfunctional (meth)acrylate (A) and the polyfunctional thiol (B).

[0059] <Photopolymerization initiator (F)> In this embodiment, it is preferable that the composition further contains a photopolymerization initiator (F). The photopolymerization initiator (F) used in this embodiment is used to efficiently advance a curing reaction caused by crosslinking of the multifunctional (meth)acrylate (A) and the multifunctional thiol (B). In the curing reaction, it is preferable to use active energy rays such as ultraviolet rays and electron beams, and more preferably ultraviolet rays. The wavelength and irradiation amount of the active energy rays can be appropriately set, and for example, ultraviolet rays having a wavelength of 280 to 400 nm can be used at 100 mJ / cm. 2 ~5000mJ / cm 2 Examples of light sources for generating ultraviolet light include known light sources such as low-pressure mercury lamps, high-pressure mercury lamps, metal halide lamps, and xenon lamps. These may be used alone or in any combination of two or more.

[0060] As the photopolymerization initiator (F) used in the present embodiment, a known photopolymerization initiator can be used, for example, acetophenones such as diethoxyacetophenone, 2-hydroxy-1-phenylpropan-1-one, benzyl methyl ketal, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butane, oligo{2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone}, 2-hydroxy-1-{4-(2-hydroxy-2-methylpropionyl)benzyl}phenyl}-2-methylpropan-1-one; Benzoins such as benzoin, benzoin methyl ether, and benzoin ethyl ether; Phosphines such as 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide; Other examples include phenyl glyoxylic methyl ester, etc. These may be used alone or in any combination of two or more.

[0061] The amount of the photopolymerization initiator (F) used in this embodiment is preferably in the range of 0.05% by mass or more and 5% by mass or less, and more preferably 0.1% by mass or more and 4% by mass or less, relative to 100% by mass of the sum of the polyfunctional (meth)acrylate (A) and the polyfunctional thiol (B).

[0062] In this embodiment, in order to further increase the curing property, a photosensitizer can be used together with the photopolymerization initiator (F). As the photosensitizer, a known photosensitizer can be used, for example, unsaturated ketones such as chalcone derivatives and dibenzalacetone, 1,2-diketones such as benzil and camphorquinone, polymethine dyes such as benzoin derivatives, fluorene derivatives, naphthoquinone derivatives, anthraquinone derivatives, xanthene derivatives, thioxanthene derivatives, xanthone derivatives, thioxanthone derivatives, coumarin derivatives, ketocoumarin derivatives, cyanine derivatives, merocyanine derivatives, and oxonol derivatives, acridine derivatives, azine derivatives, thiazine derivatives, oxazine derivatives, indoline, etc. derivatives, azulene derivatives, azulenium derivatives, squarylium derivatives, porphyrin derivatives, tetrapyrazinoporphyrazine derivatives, phthalocyanine derivatives, tetraazaporphyrazine derivatives, tetraquinoxaliroporphyrazine derivatives, naphthalocyanine derivatives, subphthalocyanine derivatives, pyrylium derivatives, thiopyrylium derivatives, tetraphylline derivatives, annulene derivatives, spiropyran derivatives, spirooxazine derivatives, thiospiropyran derivatives, metal arene complexes, organic ruthenium complexes, Michler's ketone derivatives, biimidazole derivatives, etc. These may be used alone or in any combination of two or more.

[0063] The amount of the photosensitizer used in this embodiment is preferably in the range of 0.05% by mass or more and 5% by weight or less relative to 100% by mass of the sum of the polyfunctional (meth)acrylate (A) and the polyfunctional thiol (B).

[0064] <Dispersion resin (G)> In this embodiment, it is preferable to further include a dispersion resin (G). The dispersion resin (G) used in this embodiment is used for the purpose of improving the compatibility of the quantum dots (D) and the scattering agent (E) with the multifunctional (meth)acrylate (A) and the multifunctional thiol (B). By improving the compatibility, it is possible to suppress the in-plane variation in the brightness of the cured film made of the quantum dot-containing composition, and also to suppress the decrease in the luminescence quantum yield due to the aggregation of the quantum dots (D).

[0065] The dispersion resin (G) used in the present embodiment is not limited to the following, but examples thereof include acrylic resins, polyurethane resins, polyester resins, polyolefin resins, polycarbonate resins, polyethyleneimine resins, epoxy resins, thioether resins, etc. In particular, from the viewpoint of excellent compatibility with the multifunctional (meth)acrylate (A) and the multifunctional thiol (B), it is preferable that the dispersion resin (G) is at least one selected from the group consisting of acrylic resins, polyurethane resins, polyester resins, and polyethyleneimine resins.

[0066] The acrylic resin used in the present embodiment is obtained by polymerizing a monomer having an unsaturated group such as a (meth)acrylate group, a vinyl group, or an allyl group by a known polymerization method such as radical polymerization, living radical polymerization, anionic polymerization, or cationic polymerization.

[0067] The urethane-based resin used in the present embodiment is obtained by subjecting polyol and polyisocyanate to a urethane reaction using a known method.

[0068] The polyester resin used in the present embodiment can be obtained by subjecting a polybasic acid and a polyol to an esterification reaction using a known method, or by subjecting a cyclic ester compound such as caprolactone or butyrolactone to ring-opening polymerization using a known method.

[0069] The polyolefin resin can be obtained by polymerizing an olefin monomer such as ethylene, propylene, butene, or isobutene by a known polymerization method such as coordination polymerization.

[0070] The polycarbonate resin can be obtained by subjecting a polyol and a polyfunctional carbonate such as diethyl carbonate to a carbonation reaction using a known method.

[0071] The polyethyleneimine resin can be obtained by ring-opening polymerization of an aziridine compound. In addition, a polyester resin-grafted polyethyleneimine resin can also be used, which can be obtained by reacting, for example, a cyclic ester compound with the amino group generated after the reaction and then ring-opening polymerization.

[0072] The epoxy resin can be obtained by ring-opening polymerization of a compound having two or more glycidyl groups using a known method.

[0073] In addition, from the viewpoint of effectively obtaining excellent compatibility by adsorbing to the quantum dots (D) and the scattering agent (E), the dispersing resin (G) preferably has a polar functional group such as a carboxyl group, a sulfonic acid group, a phosphoric acid group, an amino group, a mercapto group, or a hydroxyl group, and more preferably a phosphoric acid group, an amino group, or a mercapto group. These are preferable not only because they provide excellent compatibility but also because they can increase the luminescence quantum yield of the quantum dots (D).

[0074] The amount of the dispersion resin (G) used in this embodiment is preferably in the range of 0.1 mass % or more and 5 mass % or less, and more preferably in the range of 0.2 mass % or more and 4 mass % or less, relative to 100 mass % of the sum of the polyfunctional (meth)acrylate (A) and the polyfunctional thiol (B).

[0075] In this embodiment, a known organic solvent may be used as a dilution solvent for the quantum dots (D), as a reaction solvent during synthesis of the dispersion resin (G), or for the purpose of adjusting the viscosity during application of the quantum dot-containing composition. Note that the known organic solvent is preferably removed in the curing process described below.

[0076] Examples of the solvent used in the present embodiment include, but are not limited to, ester-based solvents such as ethyl acetate, propyl acetate, and butyl acetate, ketone-based solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, ether-based solvents such as dioxane and tetrahydrofuran, aliphatic hydrocarbon-based solvents such as n-hexane, cyclohexane, and methylcyclohexane, aromatic hydrocarbon-based solvents such as toluene and xylene, alcohol-based solvents such as methanol, ethanol, and isopropanol, amide-based solvents such as dimethylformamide, water, etc. These may be used alone or in any combination of two or more.

[0077] The quantum dot-containing composition in the present embodiment described above in detail includes a polyfunctional (meth)acrylate (A), a polyfunctional thiol (B), a reaction retarder (C), and a quantum dot (D), and more preferably includes at least one of a scattering agent (E), a photopolymerization initiator (F), and a dispersion resin (G). The amount of each of these substances is as described above.

[0078] In addition, a preferred embodiment of the quantum dot-containing composition in this embodiment is characterized in that it contains a multifunctional (meth)acrylate, a multifunctional thiol, a reaction retarder, and quantum dots, and the reaction retarder contains a dithiocarbamate compound. As shown in the experiment described below, by containing tetraethyl thiuram disulfide among dithiocarbamate compounds, it is possible to obtain a good pot life, as shown in the experiment described below.

[0079] In addition, a preferred embodiment of the quantum dot-containing composition in this embodiment includes a multifunctional (meth)acrylate, a multifunctional thiol, a reaction retarder, a scattering agent, a photopolymerization initiator, and a quantum dot, and is characterized in that the ratio of the molar number of the (meth)acrylate group of the multifunctional (meth)acrylate to the molar number of the mercapto group of the multifunctional thiol is in the range of 0.8 to 5.5, or the ratio of the molar number of the (meth)acrylate group of the multifunctional (meth)acrylate to the molar number of the mercapto group of the multifunctional thiol is in the range of 1.52 to 9.0. In Experimental Examples 1, 2, 5 to 11, 22, 23, and 26 to 32 described later, favorable results were obtained in terms of haze value, total light transmittance (%), durability, etc.

[0080] The quantum dot-containing composition used in this embodiment may further contain known additives depending on the purpose, as long as the effect of this embodiment is not impaired. Examples of known additives include antioxidants, ultraviolet absorbers, antistatic agents, lubricants, surface conditioners, and viscosity adjusters. These may be used alone or in any combination of two or more.

[0081] <Quantum dot-containing materials> As shown in FIG. 2, by curing the quantum dot-containing composition of the present embodiment, for example, a film-shaped quantum dot-containing member 1 containing quantum dots (D) can be obtained.

[0082] As shown in FIG. 3, for example, a quantum dot layer (ink layer) 3 obtained by curing a quantum dot-containing composition on a base film 2 such as plastic can be formed to obtain a quantum dot-containing member 1 having a laminated structure. In addition, the quantum dot-containing member 1 may have a quantum dot layer 3 formed on one side of the base film 2, but when applied to a backlight device described later, the quantum dot layer 3 is preferably in the form of a film, and from the viewpoint of excellent durability of the quantum dots (D), as shown in FIG. 4, the quantum dot-containing member 1 is preferably in the form of a laminated structure in which the base film 2 is bonded to both sides of the film-like quantum dot layer 3. When bonding the base film 2 and the quantum dot layer 3 together, they may be bonded together using a known adhesive, or they may be bonded together by using the quantum dot-containing composition of the present embodiment itself as an adhesive and curing it.

[0083] An example of a schematic diagram of the quantum dot-containing member 1 used in this embodiment is shown in Fig. 5. In Fig. 5, the quantum dot-containing member 1 is formed in a thin plate shape (sheet shape, film shape) with a length dimension L, a width dimension W, and a thickness dimension T, and L, W, and T can be changed to optimal values ​​depending on the application. The quantum dot-containing member 1 may be formed with a constant thickness, or may have a shape in which the thickness varies depending on the location, gradually changes in the length direction or width direction, or changes in a stepwise manner.

[0084] Furthermore, the quantum dot-containing member 1 used in this embodiment is formed by curing a quantum dot-containing composition, and thus, compared to the conventional method, it is possible to more effectively suppress deterioration over time and discoloration of the quantum dot layer located near the end (edge) of the quantum dot-containing member 1. The reason why deterioration can be suppressed by this embodiment is considered to be that the obtained quantum dot layer is a cured film with a high crosslink density due to the multifunctional (meth)acrylate (A) and the multifunctional thiol (B), and that the multifunctional thiol (B) can effectively suppress the intrusion of oxygen.

[0085] The base film 2 of the quantum dot-containing member 1 used in this embodiment is not limited to the following, but may be, for example, polyester, polypropylene, polyethylene, polystyrene, AS resin, ABS resin, acrylic resin, methacrylic resin, polyvinyl chloride, polyacetal, polyamide, polycarbonate, modified polyphenylene ether, polybutylene terephthalate, polyethylene terephthalate, polysulfone, polyethersulfone, polyphenylene sulfide, polyamideimide, polymethylpentene, liquid crystal polymer, epoxy resin, phenolic resin, urea resin, melamine resin, epoxy resin, diallyl phthalate resin, unsaturated polyester resin, polyimide, polyurethane, silicone resin, styrene-based thermoplastic elastomer, etc. These may be used alone or in any combination of two or more. Among them, polyester is preferable from the viewpoint of excellent light transmittance, thermal stability, dimensional stability, and adhesion between the base film 2 and the quantum dot layer 3, and more preferably polyethylene terephthalate. In order to improve the adhesion between the quantum dot layer 3 and the base film 2, the surface of the base material (the surface in contact with the quantum dot layer 3) may be subjected to a pretreatment such as a plasma treatment, a corona treatment, an ozone treatment, etc., and an adhesive layer (primer treatment) may be provided between the quantum dot layer 3 and the base film 2.

[0086] The average thickness of the base film 2 of the quantum dot-containing member 1 used in this embodiment is not limited to the following, but is preferably in the range of 50 to 150 μm, and more preferably in the range of 70 to 140 μm. The average thickness of the base film 2 is determined by averaging values ​​obtained by measuring the thickness of the base film 2 at three or more points using, for example, a micrometer.

[0087] The surface (outer surface) of the base film of the quantum dot-containing member 1 used in this embodiment may be subjected to a matte treatment in order to efficiently take in excitation light and extract emitted light.

[0088] The total light transmittance of the quantum dot-containing member 1 used in this embodiment is preferably 55% or more, and more preferably 65% ​​or more. The total light transmittance is determined by measuring in accordance with the measuring method of JIS K 7136:2000.

[0089] The haze value of the quantum dot-containing member 1 in this embodiment is preferably 85% or more, more preferably 90% or more, and even more preferably 95% or more, in terms of efficient use of the excitation light. The haze value is determined by measuring according to the measuring method of JIS K 7136:2000.

[0090] The quantum dot-containing member 1 of the present embodiment can be incorporated, for example, into a backlight device 55 shown in Fig. 6. In Fig. 6, the backlight device 55 is configured to have a plurality of light-emitting elements 20 (LEDs) and the quantum dot-containing member 1 of the present embodiment facing the light-emitting elements 20. As shown in Fig. 6, each light-emitting element 20 is supported on the surface of a support 52. In Fig. 6, the backlight device 55 is disposed on the back side of a display unit 54 such as a liquid crystal display to configure a display device 50.

[0091] Although not shown in FIG. 6, in addition to the quantum dot-containing member 1, a light diffusing plate and other sheets may be interposed between the light emitting element 20 and the display unit 54.

[0092] 6 is formed of one piece, but for example, a plurality of quantum dot-containing members 1 may be joined together to obtain a predetermined size. Hereinafter, a configuration in which a plurality of quantum dot-containing members 1 are joined together by tiling is referred to as a composite quantum dot-containing member.

[0093] Here, a configuration in which a composite quantum dot-containing member is arranged instead of the quantum dot-containing member 1 of the display device 50 in FIG. 6 and a diffuser is arranged between the light-emitting element 20 and the composite quantum dot-containing member, that is, a configuration of the light-emitting element 20 / diffuser / composite quantum dot-containing member / display unit 54, will be considered. In this configuration, the light emitted from the light-emitting element 20 and diffused by the diffuser is incident on the composite quantum dot-containing member. Since the light diffused by the diffuser is incident on the composite quantum dot-containing member, the light intensity distribution due to the distance from the light-emitting element 20 is suppressed. In addition, since the distance between the light-emitting element 20 and the composite quantum dot-containing member is longer than when there is no diffuser, the effect of the heat generated by the light-emitting element 20 on the quantum dots (D) contained in the composite sheet is reduced.

[0094] 7, the light emitting element 20 / composite quantum dot-containing member 21 / diffusion plate 22 / display unit 54 may be arranged in this order. This makes it possible to appropriately suppress color unevenness in the display of the display unit 54 even if unevenness in the emitted light occurs at the joints of the quantum dot-containing members 1 due to diffuse reflection or deterioration of the quantum dots due to water vapor entering from the joints. That is, the light emitted from the composite quantum dot-containing member 21 is diffused by the diffusion plate 22 and then incident on the display unit 54, so that color unevenness in the display of the display unit 54 can be suppressed.

[0095] When the composite quantum dot-containing member 21 is used, it is preferable to place a diffusion plate on the light exit surface side of the composite quantum dot-containing member 21, regardless of the application to the display device shown in FIG.

[0096] Alternatively, as shown in Fig. 8, a light guide member may be configured by providing the quantum dot-containing member 1 of the present embodiment on the surface of a light guide plate 40. As shown in Fig. 8, a light emitting element 20 (LED) is disposed on the side surface of the light guide plate 40.

[0097] Alternatively, as shown in FIG. 9, the quantum dot-containing member 1 of the present embodiment can be incorporated into a liquid crystal display element 60 having a structure shown in FIG. 9. The liquid crystal display element 60 of FIG. 9 is laminated in the order of, for example, a light guide plate 61, a diffusion sheet 62, a prism sheet 63, a diffusion sheet 64, a polarizing plate 65, a retardation film 66, a liquid crystal cell 67 composed of a glass substrate / liquid crystal / color filter, a retardation film 68, and a polarizing plate 69 from the bottom. Although not limited thereto, the quantum dot-containing member 1 of the present embodiment is provided, for example, between the light guide plate 61 and the diffusion sheet 62. The liquid crystal display element of FIG. 9 is an edge type in which the light of the LED is incident from the side, but may be a direct type in which multiple LEDs are arranged directly below. The direct type is used for large displays, etc.

[0098] Fig. 10 shows a structure in which the quantum dot-containing member 1 of this embodiment is incorporated into a liquid crystal display element 60 having a structure shown in Fig. 10. The same reference numerals in Fig. 10 as in Fig. 9 indicate the same components as in Fig. 9.

[0099] 10 differs from Fig. 9 in that it has a direct-type LED sheet 80 and a partial reflection sheet (partial reflection layer) 81 above the LED sheet 80. For the partial reflection sheet, "BLT" manufactured by 3M can be used.

[0100] 10, the quantum dot-containing member 1 is provided on the surface of the partial reflection sheet 81. The quantum dot-containing member 1 may be applied to the surface of the partial reflection sheet 81, or the quantum dot-containing member 1 may be a sheet and the quantum dot-containing member 1 may be attached to the surface of the partial reflection sheet 81.

[0101] The liquid crystal display element 60 of the embodiment shown in Fig. 11 is an edge type, unlike that of Fig. 10. That is, an LED (light source) is located to the side of the element, and light that enters the light guide plate from the light source is sent upward by the light guide plate. In the embodiment shown in Fig. 11, a partial reflection sheet 81 is provided on a light guide plate 61, and a quantum dot-containing member 1 is provided on the surface of the partial reflection sheet 81.

[0102] 10 and 11 transmits blue light and reflects red and green light. Alternatively, the partially reflective sheet (partially reflective layer) 81 can reflect all of the red and green light and partially reflect the blue light.

[0103] The LED emits blue light. Therefore, a part of the blue light is transmitted through the partial reflection sheet 81 and is wavelength-converted to red light and / or green light in the quantum dot-containing member 1. The wavelength-converted red light and green light are emitted upward by the partial reflection sheet 81, not downward.

[0104] Here, when a blue LED is used, in a configuration without the partial reflection sheet 81, when the blue light is wavelength-converted by the quantum dot-containing member 1, color unevenness and brightness unevenness (halo phenomenon) may occur due to diffusion, irregular reflection, etc. Therefore, by providing the partial reflection sheet 81 as in this embodiment, it is possible to suppress the halo phenomenon. In particular, as shown in FIG. 10, this is effective when the number of LEDs is increased in a direct type. In addition, by reducing the transmission of blue light by the partial reflection sheet 81, the amount of reused blue light can be increased, and the brightness (luminous intensity) can be improved. Therefore, high brightness can be obtained even if the quantum dots do not contain regulated heavy metals such as Cd and Pb. The applications of the quantum dot-containing member 1 of this embodiment are not limited to those shown in FIGS.

[0105] The quantum dot-containing member 1 used in this embodiment can suppress the change in emission intensity over time more effectively than in the past. Therefore, when the quantum dot-containing member 1 of this embodiment is used in a backlight device 55, a light guide member, a liquid crystal display element, etc., the wavelength conversion characteristics can be stabilized, and the life of the backlight device 55, the light guide member, and the liquid crystal display element can be extended.

[0106] The quantum dot-containing member 1 used in this embodiment may be in the form of a flexible sheet, and therefore the quantum dot-containing member 1 may be appropriately placed on a curved surface or the like.

[0107] The quantum dot-containing member 1 of the present embodiment can be applied to lighting devices, light source devices, light diffusing devices, light reflecting devices, etc., in addition to the above-mentioned backlight devices, light guide members, and liquid crystal display elements.

[0108] The quantum dot-containing member 1 used in this embodiment can ensure a normalized illuminance of 0.6 or more after 1000 hours of durability testing, preferably a normalized illuminance of 0.75 or more, more preferably a normalized illuminance of 0.85 or more, and even more preferably a normalized illuminance of 0.9 or more.

[0109] 12, the quantum dot-containing member 1 of the present embodiment can have a structure in which the base film 2 is provided only on one side of the quantum dot layer 3, and the optical member 70 is in contact with the surface of the quantum dot layer 3 opposite the base film 2. This allows the optical member 70 to be in close contact with the surface opposite the quantum dot layer 3 while protecting one side of the quantum dot layer 3 with the base film 2. A light guide plate or a diffusion plate can be preferably used as the optical member 70. This quantum dot-containing member 1 can be used in a backlight device, a display device, or a lighting device.

[0110] The quantum dot-containing member 1 shown in FIG. 12 can be formed by directly applying the quantum dot-containing composition of the present embodiment to the surface of the optical member 70, overlaying the substrate film 2, and thermally curing the composition to form a laminated structure of the optical member / quantum dot layer / substrate film.

[0111] 13, the surface of a quantum dot-containing sheet 71 having a base film 2 provided only on one side of a quantum dot layer 3 on which the base film 2 is not provided is placed opposite an optical member 70, and the quantum dot-containing sheet 71 and the optical member 70 are brought into close contact with each other. At this time, the quantum dot-containing sheet 71 and the optical member 70 may be joined via an adhesive layer, or the quantum dot-containing sheet 71 may be directly brought into close contact with the surface of the optical member 70.

[0112] As shown in FIG. 14A, the quantum dot-containing sheet 71 has, for example, a first base film 73 bonded to one side of the quantum dot layer 3 via a primer layer 72, and a second base film 74 bonded directly to the surface of the quantum dot layer 3 opposite to the first base film 73. This allows both sides of the quantum dot layer 3 to be protected by the base films 73 and 74. As an example, the base films 73 and 74 can be formed of PET films. Also, the first base film 73 can be a PET film, and the second base film 74 can be a PE film. Alternatively, a PEN (polyethylene naphthalate) film may be used instead of the PET film or PE film.

[0113] In the quantum dot-containing sheet 71, the adhesion between the first base film 72 and the quantum dot layer 3 is stronger than the adhesion between the second base film 73 and the quantum dot layer 3. Then, as shown in Fig. 13, in the stage of attaching the quantum dot-containing sheet 71 to the surface of the optical member 70, a process of peeling off the second base film 73 of the quantum dot-containing sheet 71 and a process of attaching the surface of the quantum dot layer 3 exposed by the peeling to the surface of the optical member 70 are performed, whereby the quantum dot-containing member 1 shown in Fig. 12 can be obtained.

[0114] A conceptual diagram showing a manufacturing apparatus for manufacturing the quantum dot-containing member 1 of the present embodiment is shown in Fig. 15. Fig. 15 discloses an example of a manufacturing method for the quantum dot-containing member 1 in which a quantum dot layer 3 is formed by applying a quantum dot-containing composition to a base film 2 shown in Fig. 4 and curing the composition.

[0115] As shown in Figure 15, the apparatus is configured to include a first original roll 30a that feeds out a resin film 10a that becomes the base film 2, a second original roll 30b that feeds out a resin film 10b that similarly becomes the base film 2, a take-up roll 32, a joining section 35 formed by a pair of nip rolls 33, 34, an application means 36, a drying section 38, and a curing reaction section 40.

[0116] As shown in Fig. 15, a resin film 10a is fed from a first original roll 30a, and a quantum dot-containing composition 37 containing quantum dots (D) is applied to the surface of the resin film 10a using a coating means 36. Examples of a method for applying the quantum dot-containing composition 37 include a coating method using a known coating coater or an impregnation coating coater. Examples include a gravure coater, a curtain coater, a dip coater, a comma knife coater, a die coater, and a roll coater.

[0117] 15, the resin film 10a having the quantum dot-containing composition 37 applied thereon is heated by a drying section 38 having a heating device such as a heater or a hot air oven, and the solvent contained therein is volatilized. If the quantum dot-containing composition 37 does not contain a solvent, the drying section 38 does not need to be used.

[0118] Next, in the bonding section 35, the interface between the quantum dot-containing composition 37 applied to the resin film 10a and the resin film 10b fed from the second original roll 30b is bonded by a pressure bonding device. During bonding, temperature may be applied as necessary. Note that if the quantum dot layer 3 is not sandwiched between the resin film 10a and the resin film 10b, the above bonding operation does not need to be performed.

[0119] Next, the layer is irradiated with active energy rays in a curing reaction section 40 in which an active energy ray irradiator such as an ultraviolet ray irradiator or an electron beam irradiator is installed, thereby forming a hardened quantum dot layer 3 (see FIG. 4). The active energy ray irradiation may be performed before or after the bonding step in the bonding section 35.

[0120] Then, a sheet-like quantum dot-containing member 39 consisting of the resin film 10a / quantum dot layer 3 / resin film 10b is taken up by a take-up roll 32. The taken-up quantum dot-containing member 39 is cut to a predetermined size to obtain the quantum dot-containing member 1 having a predetermined shape as shown in Fig. 4. The quantum dot-containing composition 37 of this embodiment has an excellent pot life, and the quantum dot-containing member 39 can be mass-produced.

[0121] In order to completely proceed with the curing reaction, the quantum dot-containing member 1 of the present embodiment can be aged for an appropriate time in an environment at an appropriate aging temperature. The appropriate aging temperature is not limited to the following, but is preferably in the range of 20 to 60° C., and more preferably in the range of 30 to 50° C. The appropriate aging time is preferably in the range of 6 to 48 hours, and more preferably in the range of 10 to 24 hours.

[0122] The average thickness of the quantum dot layer 3 in the quantum dot-containing member 1 of this embodiment is not limited to the following, but is preferably in the range of 20 to 250 μm, more preferably in the range of 50 to 200 μm, and even more preferably in the range of 70 to 140 μm. When the average thickness is 20 to 250 μm, sufficient wavelength conversion efficiency can be obtained. The average thickness of the quantum dot layer 3 in the quantum dot-containing member 1 is calculated by, for example, subtracting the average thickness of half the base film used from the average thickness measured at three or more points of the quantum dot-containing member 1 using a micrometer.

[0123] In addition, by using the manufacturing apparatus shown in FIG. 15, it is possible to manufacture a quantum dot-containing film member 71 in which a primer layer 72 is provided on only one side of the quantum dot layer 3, as shown in FIG. 14B, and the adhesion strength between the quantum dot layer 3 and the base films 72, 73 is made different.

[0124] In addition, it is possible to manufacture a quantum dot-containing film member in which a base film is provided on only one side of a quantum dot layer by using the manufacturing apparatus shown in Fig. 15. In this case, it is not necessary to use the second original roll 30b and the nip rolls 33 and 34.

[0125] In the above embodiments, the quantum dot-containing member is in the form of a film, but the shape is not limited thereto. For example, a stick-shaped object obtained by filling a glass capillary with the quantum dot-containing composition used in the present invention or inserting a cured product of the quantum dot-containing composition, a form in which the quantum dot-containing composition is coated on the surface of an LED by potting or the like, or a quantum dot-containing member obtained by curing a quantum dot-containing composition by an inkjet method can be presented. EXAMPLES

[0126] The effects of the present invention will be described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0127] <Measurement of number average molecular weight> The number average molecular weight was measured by gel permeation chromatography (GPC) using the dispersion resin (G) as a sample. For samples soluble in tetrahydrofuran, tetrahydrofuran was used as the eluent, and the measurement was performed using a Tosoh Corporation HLC-8220GPC system connected to two TSKgel superHZM-N columns at a column temperature of 40°C and a flow rate of 0.35 ml per minute. The sample was prepared by dissolving 2 mg of the sample in 5 ml of the above eluent. The number average molecular weight was calculated in terms of standard polystyrene. The number average molecular weight was not calculated for samples that were insoluble in the eluent or samples that could not be measured due to adsorption to the column, etc.

[0128] <Quantum yield measurement> Using the quantum dots (D) and quantum dot-containing materials described below as samples, the quantum yield of luminescence was measured at an excitation wavelength of 450 nm using an absolute PL quantum yield measurement device (Quantaurus-QY C11347-01, manufactured by Hamamatsu Photonics K.K.) Note that for the quantum dots (D), a toluene solution was prepared so that the absorbance at 450 nm when using a 1 cm cell was 1, and used as the sample.

[0129] <Measurement of emission peak wavelength and half-width> Using quantum dots (D) described later as samples, the emission peak wavelength and half-width were measured using a spectrofluorophotometer (JASCO Corporation, FP-8500) with an excitation wavelength of 450 nm. Note that for quantum dots (D), a toluene solution was prepared so that the absorbance at 450 nm when using a 1 cm cell was 1.

[0130] <Viscosity measurement> Using a quantum dot-containing composition described below as a sample, viscosity was measured at 25° C. using a Brookfield viscometer (TVB-10M, manufactured by Toki Sangyo Co., Ltd.).

[0131] <Film thickness measurement> The thickness of the quantum dot-containing member obtained as described below was measured at three or more points using a micrometer (high-precision digital micrometer MDH-25MB, manufactured by Mitutoyo Corporation), and the average value was calculated.

[0132] <Measurement of total light transmittance and haze> The quantum dot-containing member obtained as described below was cut into a sample having a width of 50 mm and a length of 50 mm, and the total light transmittance and haze value were measured three times using a spectroscopic haze meter (SH7000, manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with the measurement method of JIS K 7136: 2000. The average values ​​of the three measurements were used as the total light transmittance and haze value.

[0133] <Quantum dots (D)> In the experiments, powder of quantum dots (hereinafter referred to as green quantum dots) with an emission peak wavelength of 530 nm (green), a half-width of 30 nm, and an emission quantum yield of 90% in toluene solution, and powder of quantum dots (hereinafter referred to as red quantum dots) with an emission peak wavelength of 630 nm (red), a half-width of 30 nm, and an emission quantum yield of 90% in toluene solution were used.

[0134] <Production of Dispersion Resin (G)> Dispersion resins (G-1) to (G-6) were produced according to the following method. Table 1 shows the raw materials and their amounts used, as well as the properties of the resulting dispersion resins.

[0135] <Production Example (1)> In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tube, and a nitrogen inlet tube, 25.8 parts of toluene, 56.6 parts of n-butyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), and 3.5 parts of pentaerythritol tetrakis (3-mercaptopropionate) (manufactured by Tokyo Chemical Industry Co., Ltd.) were charged while blowing nitrogen gas into the reaction vessel, and the mixture was stirred at room temperature for 30 minutes. Next, after heating to 90 ° C, a solution in which 0.02 parts of 2,2'-azobis (isobutyronitrile) was dissolved in 2.5 parts of toluene was dropped over 6 hours, and then the mixture was stirred for another 3 hours at 90 ° C to cause a polymerization reaction. After that, the reaction solution was taken out after cooling to room temperature, and the solvent was removed by vacuum drying to obtain a solid dispersion resin (G-1). Note that "parts" means "parts by mass". The same applies to the following experiments.

[0136] The dispersion resin (G-1) thus obtained was an acrylic resin having a number average molecular weight of 2,500 and containing a mercapto group.

[0137] <Production Example (2)> A reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tube, and a nitrogen inlet tube was charged with 25.7 parts of toluene, 28.9 parts of n-butyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), 28.9 parts of 2-ethylhexyl methacrylate, and 2.1 parts of pentaerythritol tetrakis (3-mercaptopropionate) (manufactured by Tokyo Chemical Industry Co., Ltd.) while blowing nitrogen gas into the reaction vessel, and stirred at room temperature for 30 minutes. Next, after heating to 90 ° C, a solution in which 0.02 parts of 2,2'-azobis (isobutyronitrile) was dissolved in 2.5 parts of toluene was dropped over 6 hours, and then the polymerization reaction was carried out by stirring for another 3 hours at 90 ° C. After that, the reaction solution was cooled to room temperature, and the solvent was removed by vacuum drying to obtain a viscous liquid of a dispersion resin (G-2).

[0138] The dispersion resin (G-2) thus obtained was an acrylic resin having a number average molecular weight of 3,300 and containing a mercapto group.

[0139] <Production Example (3)> In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a nitrogen inlet tube, and a vacuum pipe, 86.9 parts of pentaerythritol tetrakis (3-mercaptopropionate) (manufactured by Tokyo Chemical Industry Co., Ltd.) were charged, and the inside of the reaction vessel was depressurized with a vacuum pump while stirring, and the reaction vessel was maintained for 30 minutes. After that, 13.0 parts of tris (2-acryloyloxyethyl) isocyanurate (manufactured by Tokyo Chemical Industry Co., Ltd.) heated to 60 ° C. was added while stirring, and after stirring until it became uniform, 0.1 parts of triethylamine was added, and the mixture was stirred and reacted for 3 hours to obtain a viscous liquid of dispersion resin (G-3). The dispersion resin (G-3) thus obtained was a thioether resin having a number average molecular weight of 2,100 and containing a mercapto group.

[0140] <Production Example (4)> As the dispersion resin (G-4), SOLSPERSE (registered trademark) 24000GR (manufactured by Lubrizol Japan, a polyethyleneimine-based resin having an amino group) was used.

[0141] <Production Example (5)> As the dispersion resin (G-5), AJISPER (registered trademark) PB821 (manufactured by Ajinomoto Fine-Techno Co., Ltd., polyester resin having an amino group) was used.

[0142] <Production Example (6)> As the dispersion resin (G-6), DISPERBYK (registered trademark)-111 (manufactured by BYK Japan, polyester resin having a phosphoric acid group) was used.

[0143] [Table 1]

[0144] <Production of Quantum Dot-Containing Composition> Quantum dot-containing compositions (X-1) to (X-21) were produced according to the method described below. Tables 2 and 3 show the amounts of raw materials used in the production and the results of the pot life evaluation described below.

[0145] <Experimental Example 1> As the multifunctional (meth)acrylate (A), 60 parts of A-DCP (manufactured by Shin-Nakamura Chemical Co., Ltd., dimethylol-tricyclodecane diacrylate, (meth)acrylate group amount 6.58 mmol / g) and as the multifunctional thiol (B), EGMP-4 (manufactured by SC Organic Chemical Co., Ltd., tetraethylene glycol) were used. A mixture of 40 parts of bis(3-mercaptopropionate), mercapto group amount 5.38 mmol / g, 1 part of hydroquinone (Tokyo Chemical Industry Co., Ltd.) as a reaction retarder (C), 0.4 parts of green quantum dots and 0.07 parts of red quantum dots as quantum dots (D), 5 parts of Eposter (registered trademark) MS (Nippon Shokubai Co., Ltd., benzoguanamine-formaldehyde condensate particles) as a scattering agent (E), 0.3 parts of Irgacure (registered trademark) 184 (BASF) as a photopolymerization initiator (F), and 1.37 parts of dispersion resin (G-1) as a dispersion resin (G) was mixed and gently shaken by hand, followed by stirring with a homodisper until the entire mixture was uniform. In the quantum dot-containing composition (X-1) thus obtained, the ratio of the number of moles of (meth)acrylate groups in the multifunctional (meth)acrylate (A) to the number of moles of mercapto groups in the multifunctional thiol (B) was 1.84.

[0146] <Experimental Example 2> As the multifunctional (meth)acrylate (A), 50 parts of A-TMPT (manufactured by Shin-Nakamura Chemical Co., Ltd., trimethylolpropane triacrylate, (meth)acrylate group amount 10.0 mmol / g) and 5 parts of Shikou UV-7650B (Nippon Synthetic, urethane acrylate resin, acrylate group amount 0.0004 parts) were used. As the multifunctional thiol (B), TMMP (manufactured by SC Organic Chemical Co., Ltd., trimethylolpropane tris(3-mercaptopropionate), mercapto group amount 7.53 mmol / g) were used. ) 45 parts, triphenyl phosphite (manufactured by Tokyo Chemical Industry Co., Ltd.) 0.5 parts as a reaction retarder (C), quantum dots (D) 0.4 parts of green quantum dots, 0.07 parts of red quantum dots, Eposter MS (manufactured by Nippon Shokubai Co., Ltd., benzoguanamine-formaldehyde condensate particles) 5 parts as a scattering agent (E), Irgacure 184 (manufactured by BASF) 0.6 parts as a photopolymerization initiator (F), mixed, lightly shaken by hand, and then stirred with a homodisper until the whole was uniform. The ratio of the number of moles of (meth)acrylate groups of the multifunctional (meth)acrylate (A) to the number of moles of mercapto groups of the multifunctional thiol (B) in the quantum dot-containing composition (X-2) thus obtained was 1.48.

[0147] <Experimental Example 3> As the multifunctional (meth)acrylate (A), 20 parts of A-TMPT (manufactured by Shin-Nakamura Chemical Co., Ltd., trimethylolpropane triacrylate, (meth)acrylate group amount 10.0 mmol / g), 30 parts of AD-TMP (manufactured by Shin-Nakamura Chemical Co., Ltd., ditrimethylolpropane tetraacrylate, (meth)acrylate group amount 8.51 mmol / g), 50 parts of PEMP (manufactured by SC Organic Chemical Co., Ltd., pentaerythritol tetrakis(3-mercaptopropionate), mercapto group amount 8.19 mmol / g) as the multifunctional thiol (B), and reaction delay As the agent (C), 0.002 parts of tetraethyl thiuram disulfide (manufactured by Tokyo Chemical Industry Co., Ltd.), as quantum dots (D), 0.4 parts of green quantum dots, 0.07 parts of red quantum dots, 5 parts of Techpolymer (registered trademark) MBX-5 (manufactured by Sekisui Chemical Co., Ltd., crosslinked polymethyl methacrylate particles) as scattering agent (E), 0.2 parts of Irgacure 184 (manufactured by BASF) as photopolymerization initiator (F), 1.37 parts of dispersion resin (G-4) as dispersion resin (G), and after shaking lightly by hand, the mixture was stirred with a homodisper until the whole was uniform. The ratio of the number of moles of the (meth)acrylate group of the multifunctional (meth)acrylate (A) to the number of moles of the mercapto group of the multifunctional thiol (B) in the quantum dot-containing composition (X-3) thus obtained was 1.12.

[0148] <Experimental Example 4> As the multifunctional (meth)acrylate (A), 45 parts of AD-TMP (manufactured by Shin-Nakamura Chemical Co., Ltd., ditrimethylolpropane tetraacrylate, (meth)acrylate group amount 8.51 mmol / g) were used. As the multifunctional thiol (B), 40 parts of PEMP (manufactured by SC Organic Chemical Co., Ltd., pentaerythritol tetrakis(3-mercaptopropionate), mercapto group amount 8.19 mmol / g) and 40 parts of DPMP (manufactured by SC Organic Chemical Co., Ltd., dipentaerythritol hexakis(3-mercaptopropionate), mercapto group amount 7.66 mmol / g) were used. ) 15 parts, triphenyl phosphite (Tokyo Chemical Industry Co., Ltd.) 0.3 parts as a reaction retarder (C), quantum dots (D) 0.4 parts green quantum dots, 0.07 parts red quantum dots, D-918 (Sakai Chemical Industry Co., Ltd., rutile type titanium oxide) 0.25 parts as a scattering agent (E), Optobeads (registered trademark) 2000M (Nissan Chemical Co., Ltd., melamine resin-silica composite particles) 4 parts, Irgacure TPO (BASF) 0.3 parts as a photopolymerization initiator (F), and dispersion resin (G-6) 1.37 parts as a dispersion resin (G) were mixed, and after shaking lightly by hand, the whole was stirred with a homodisper until it became uniform. The ratio of the number of moles of the acrylate group of the multifunctional (meth)acrylate (A) to the number of moles of the mercapto group of the multifunctional thiol (B) of the quantum dot-containing composition (X-4) obtained in this way was 0.87.

[0149] <Experimental Example 5> As the multifunctional (meth)acrylate (A), 80 parts of A-TMPT (manufactured by Shin-Nakamura Chemical Co., Ltd., trimethylolpropane triacrylate, (meth)acrylate group amount 10.0 mmol / g), as the multifunctional thiol (B), 20 parts of TMMP (manufactured by SC Organic Chemical Co., Ltd., trimethylolpropane tris(3-mercaptopropionate), mercapto group amount 7.53 mmol / g), as the reaction retarder (C), 0.001 parts of tetraethyl thiuram disulfide (manufactured by Tokyo Chemical Industry Co., Ltd.), quantum As the dots (D), 0.4 parts of green quantum dots, 0.07 parts of red quantum dots, 0.2 parts of D-918 (manufactured by Sakai Chemical Industry Co., Ltd., R-type titanium oxide) as scattering agent (E), 6 parts of Optobeads 2000M (manufactured by Nissan Chemical Co., Ltd., melamine resin-silica composite particles), 0.8 parts of Irgacure TPO (manufactured by BASF) as photopolymerization initiator (F), 1.37 parts of dispersion resin (G-6) as dispersion resin (G) were mixed, and after shaking lightly by hand, the whole was stirred with a homodisper until it became uniform. The ratio of the number of moles of (meth)acrylate groups of the multifunctional (meth)acrylate (A) to the number of moles of mercapto groups of the multifunctional thiol (B) in the quantum dot-containing composition (X-5) thus obtained was 5.31.

[0150] <Experimental Example 6> As the multifunctional (meth)acrylate (A), 50 parts of A-TMPT (manufactured by Shin-Nakamura Chemical Co., Ltd., trimethylolpropane triacrylate, (meth)acrylate group amount 10.0 mmol / g) and 5 parts of A-DPH (manufactured by Shin-Nakamura Chemical Co., Ltd., dipentaerythritol hexaacrylate, (meth)acrylate group amount 0.010 mmol / g) were used. As the multifunctional thiol (B), 35 parts of PEMP (manufactured by SC Organic Chemical Co., Ltd., pentaerythritol tetrakis(3-mercaptopropionate), mercapto group amount 8.19 mmol / g) and 35 parts of DPMP (manufactured by SC Organic Chemical Co., Ltd., dipentaerythritol hexakis(3-mercaptopropionate), mercapto group amount 7.66 mmol / g) were used. ) 10 parts, triphenyl phosphite (Tokyo Chemical Industry Co., Ltd.) 0.3 parts as a reaction retarder (C), quantum dots (D) 0.4 parts green quantum dots, 0.07 parts red quantum dots, Eposter MS (Nippon Shokubai Co., Ltd., benzoguanamine-formaldehyde condensate particles) 7 parts as a scattering agent (E), Irgacure 184 (BASF) 0.8 parts as a photopolymerization initiator (F), and dispersion resin (G-3) 1.37 parts as a dispersion resin (G-3) were mixed, and after shaking lightly by hand, the whole was stirred with a homodisper until it became uniform. The ratio of the number of moles of the (meth)acrylate group of the multifunctional (meth)acrylate (A) to the number of moles of the mercapto group of the multifunctional thiol (B) in the quantum dot-containing composition (X-6) thus obtained was 1.52.

[0151] <Experimental Example 7> As the polyfunctional (meth)acrylate (A), 50 parts of A-TMPT (manufactured by Shin-Nakamura Chemical Co., Ltd., trimethylolpropane triacrylate, (meth)acrylate group amount 10.0 mmol / g), 15 parts of AD-TMP (manufactured by Shin-Nakamura Chemical Co., Ltd., trimethylolpropane triacrylate, (meth)acrylate group amount 10.0 mmol / g), 35 parts of PEMP (manufactured by SC Organic Chemical Co., Ltd., pentaerythritol tetrakis (3-mercaptopropionate), mercapto group amount 8.19 mmol / g) as the polyfunctional thiol (B), and reaction delay As the agent (C), 0.002 parts of tetraethyl thiuram disulfide (manufactured by Tokyo Chemical Industry Co., Ltd.), as quantum dots (D), 0.4 parts of green quantum dots, 0.07 parts of red quantum dots, as scattering agent (E), 1.0 parts of D-918 (manufactured by Sakai Chemical Industry Co., Ltd., rutile type titanium oxide) as scattering agent (E), 0.4 parts of Irgacure 184 (manufactured by BASF) as photopolymerization initiator (F), 1.0 parts of dispersion resin (G-1) as dispersion resin (G-6) as dispersion resin (G), 1.37 parts of dispersion resin (G-6) were mixed, and after shaking lightly by hand, the whole was stirred with a homodisper until it became uniform. The ratio of the number of moles of the (meth)acrylate group of the multifunctional (meth)acrylate (A) to the number of moles of the mercapto group of the multifunctional thiol (B) of the quantum dot-containing composition (X-7) thus obtained was 2.19.

[0152] <Example 8> As the multifunctional (meth)acrylate (A), 40 parts of A-TMPT (manufactured by Shin-Nakamura Chemical Co., Ltd., trimethylolpropane triacrylate, (meth)acrylate group amount 10.0 mmol / g) and 15 parts of AD-TMP (manufactured by Shin-Nakamura Chemical Co., Ltd., ditrimethylolpropane tetraacrylate, (meth)acrylate group amount 8.51 mmol / g) were used. As the multifunctional thiol (B), Karenz (registered trademark) MT 45 parts of PE1 (Showa Denko, pentaerythritol tetrakis (3-mercaptobutyrate), mercapto group amount 7.34 mmol / g), 0.002 parts of tetraethyl thiuram disulfide (Tokyo Chemical Industry Co., Ltd.) as a reaction retarder (C), 0.4 parts of green quantum dots and 0.07 parts of red quantum dots as quantum dots (D), 5 parts of Eposter MS (Nippon Shokubai, benzoguanamine formaldehyde condensate particles) as a scattering agent (E), 0.3 parts of Irgacure 184 (BASF) as a photopolymerization initiator (F), and 1.37 parts of dispersion resin (G-2) as a dispersion resin (G) were mixed, shaken lightly by hand, and then stirred with a homodisper until the whole was uniform. In the quantum dot-containing composition (X-8) thus obtained, the ratio of the number of moles of (meth)acrylate groups in the multifunctional (meth)acrylate (A) to the number of moles of mercapto groups in the multifunctional thiol (B) was 1.60.

[0153] <Example 9> As the polyfunctional (meth)acrylate (A), 50 parts of A-TMPT (manufactured by Shin-Nakamura Chemical Co., Ltd., trimethylolpropane triacrylate, (meth)acrylate group amount 10.0 mmol / g) and 10 parts of AD-TMP (manufactured by Shin-Nakamura Chemical Co., Ltd., ditrimethylolpropane tetraacrylate, (meth)acrylate group amount 8.51 mmol / g) were used. As the polyfunctional thiol (B), 40 parts of PEMP (manufactured by SC Organic Chemical Co., Ltd., pentaerythritol tetrakis(3-mercaptopropionate), mercapto group amount 8.19 mmol / g) were used. As the reaction retarder (C), tetraethylthiuramdisulfide was used. 0.003 parts of Rufido (Tokyo Chemical Industry Co., Ltd.), 0.4 parts of green quantum dots as quantum dots (D), 0.07 parts of red quantum dots, 0.2 parts of D-918 (Sakai Chemical Industry Co., Ltd., rutile type titanium oxide) as scattering agent (E), 4.5 parts of Optobeads 2000M (Nissan Chemical Co., Ltd., melamine resin-silica composite particles), 0.2 parts of Irgacure 184 (BASF) as photopolymerization initiator (F), 0.1 parts of Irgacure TPO, 1.37 parts of dispersion resin (G-4) as dispersion resin (G), and after shaking lightly by hand, the mixture was stirred with a homodisper until the whole was uniform. The ratio of the number of moles of (meth)acrylate groups of the multifunctional (meth)acrylate (A) to the number of moles of mercapto groups of the multifunctional thiol (B) in the quantum dot-containing composition (X-9) thus obtained was 1.79.

[0154] <Experimental Example 10> As the polyfunctional (meth)acrylate (A), 50 parts of A-TMPT (manufactured by Shin-Nakamura Chemical Co., Ltd., trimethylolpropane triacrylate, (meth)acrylate group amount 10.0 mmol / g) and 10 parts of AD-TMP (manufactured by Shin-Nakamura Chemical Co., Ltd., ditrimethylolpropane tetraacrylate, (meth)acrylate group amount 8.51 mmol / g) were used. As the polyfunctional thiol (B), 40 parts of PEMP (manufactured by SC Organic Chemical Co., Ltd., pentaerythritol tetrakis(3-mercaptopropionate), mercapto group amount 8.19 mmol / g) were used. As the reaction retarder (C), tetraethylthiuramdisulfide was used. 0.003 parts of Rufido (Tokyo Chemical Industry Co., Ltd.), 0.4 parts of green quantum dots as quantum dots (D), 0.07 parts of red quantum dots, 0.2 parts of D-918 (Sakai Chemical Industry Co., Ltd., rutile type titanium oxide) as scattering agent (E), 4.5 parts of Optobeads 2000M (Nissan Chemical Co., Ltd., melamine resin-silica composite particles), 0.2 parts of Irgacure 184 (BASF) as photopolymerization initiator (F), 0.1 parts of Irgacure TPO, 1.37 parts of dispersion resin (G-5) as dispersion resin (G), and after shaking lightly by hand, the mixture was stirred with a homodisper until the whole was uniform. The ratio of the number of moles of acrylate groups of the multifunctional (meth)acrylate (A) to the number of moles of mercapto groups of the multifunctional thiol (B) in the quantum dot-containing composition (X-10) thus obtained was 1.79.

[0155] <Experimental Example 11> As the multifunctional (meth)acrylate (A), 50 parts of A-TMPT (manufactured by Shin-Nakamura Chemical Co., Ltd., trimethylolpropane triacrylate, (meth)acrylate group amount 10.0 mmol / g) and 10 parts of AD-TMP (manufactured by Shin-Nakamura Chemical Co., Ltd., ditrimethylolpropane tetraacrylate, (meth)acrylate group amount 8.51 mmol / g) were used. As the multifunctional thiol (B), 30 parts of PEMP (manufactured by SC Organic Chemical Co., Ltd., pentaerythritol tetrakis(3-mercaptopropionate), mercapto group amount 8.19 mmol / g) and DPMP (manufactured by SC Organic Chemical Co., Ltd., dipentaerythritol hexakis(3-mercaptopropionate), mercapto group amount 7.66 mmol / g) were used. ) as a reaction retarder (C), 0.003 parts of tetraethyl thiuram disulfide (Tokyo Chemical Industry Co., Ltd.), 0.4 parts of green quantum dots and 0.07 parts of red quantum dots as quantum dots (D), 0.2 parts of D-918 (Sakai Chemical Industry Co., Ltd., rutile type titanium oxide) as a scattering agent (E), 4.5 parts of Optobeads 2000M (Nissan Chemical Co., Ltd., melamine resin-silica composite particles), 0.2 parts of Irgacure 184 (BASF) as a photopolymerization initiator (F), 0.1 parts of Irgacure TPO, and 1.37 parts of dispersion resin (G-6) as a dispersion resin (G) were mixed, and the mixture was gently shaken by hand, and then stirred with a homodisper until the whole was uniform. In the quantum dot-containing composition (X-11) thus obtained, the ratio of the number of moles of (meth)acrylate groups in the multifunctional (meth)acrylate (A) to the number of moles of mercapto groups in the multifunctional thiol (B) was 1.82.

[0156] <Experimental Example 12> As the polyfunctional (meth)acrylate (A), 100 parts of A-TMPT (manufactured by Shin-Nakamura Chemical Co., Ltd., trimethylolpropane triacrylate, (meth)acrylate group amount 10.0 mmol / g) were mixed, as the reaction retarder (C), 0.002 parts of tetraethyl thiuram disulfide (manufactured by Tokyo Chemical Industry Co., Ltd.), as the quantum dots (D), 0.4 parts of green quantum dots, 0.07 parts of red quantum dots, as the scattering agent (E), 5 parts of Eposter MS (manufactured by Nippon Shokubai Co., Ltd., benzoguanamine-formaldehyde condensate particles) were mixed, as the photopolymerization initiator (F), 0.4 parts of Irgacure 184 (manufactured by BASF), and as the dispersion resin (G), 1.37 parts of dispersion resin (G-6) were mixed, and after shaking lightly by hand, the whole was stirred with a homodisper until it became uniform. In the quantum dot-containing composition (X-12) thus obtained, the ratio of the number of moles of (meth)acrylate groups in the multifunctional (meth)acrylate (A) to the number of moles of mercapto groups in the multifunctional thiol (B) was 1 / 0 (infinity due to division by zero).

[0157] <Experimental Example 13> 100 parts of TMMP (manufactured by SC Organic Chemicals, trimethylolpropane tris(3-mercaptopropionate), mercapto group amount 7.53 mmol / g) as polyfunctional thiol (B), 0.002 parts of tetraethyl thiuram disulfide (manufactured by Tokyo Chemical Industry Co., Ltd.) as reaction retarder (C), 0.4 parts of green quantum dots and 0.07 parts of red quantum dots as quantum dots (D), 5 parts of Eposter MS (manufactured by Nippon Shokubai, benzoguanamine-formaldehyde condensate particles) as scattering agent (E), 0.4 parts of Irgacure 184 (manufactured by BASF) as photopolymerization initiator (F), and 1.37 parts of dispersion resin (G-6) as dispersion resin (G) were mixed, and after shaking lightly by hand, the whole was stirred uniformly with a homodisper. In the quantum dot-containing composition (X-13) thus obtained, the ratio of the number of moles of (meth)acrylate groups in the multifunctional (meth)acrylate (A) to the number of moles of mercapto groups in the multifunctional thiol (B) was 0.

[0158] <Experimental Example 14> As the multifunctional thiol (B), 50 parts of PEMP (manufactured by SC Organic Chemicals, pentaerythritol tetrakis(3-mercaptopropionate), mercapto group amount 8.19 mmol / g) were used. As other compounds, 50 parts of isobornyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd., (meth)acrylate group amount 4.50 mmol / g) were used. As the reaction retarder (C), 0.002 parts of tetraethyl thiuram disulfide (manufactured by Tokyo Chemical Industry Co., Ltd.) were used. As the dots (D), 0.4 parts of green quantum dots, 0.07 parts of red quantum dots, 5 parts of Eposter MS (manufactured by Nippon Shokubai Co., Ltd., benzoguanamine-formaldehyde condensate particles) as scattering agent (E), 0.4 parts of Irgacure 184 (manufactured by BASF Co., Ltd.) as photopolymerization initiator (F), and 1.37 parts of dispersion resin (G-6) as dispersion resin (G) were mixed, and after shaking lightly by hand, the mixture was stirred with a homodisper until the whole was uniform. The ratio of the number of moles of (meth)acrylate groups of the multifunctional (meth)acrylate (A) to the number of moles of mercapto groups of the multifunctional thiol (B) in the quantum dot-containing composition (X-14) thus obtained was 0.

[0159] <Experimental Example 15> 50 parts of AD-TMP (manufactured by Shin-Nakamura Chemical Co., Ltd., ditrimethylolpropane tetraacrylate, acrylate group amount 8.51 mmol / g) as multifunctional (meth)acrylate (A), 50 parts of octyl thioglycolate (manufactured by Tokyo Chemical Industry Co., Ltd., mercapto group amount 4.89 mmol / g) as other compounds, 0.5 parts of triphenyl phosphite (manufactured by Tokyo Chemical Industry Co., Ltd.) as reaction retarder (C), 0.4 parts of green quantum dots as quantum dots (D), 0.07 parts of red quantum dots, 5 parts of Eposter MS (manufactured by Nippon Shokubai Co., Ltd., benzoguanamine-formaldehyde condensate particles) as scattering agent (E), 0.4 parts of Irgacure 184 (manufactured by BASF) as photopolymerization initiator (F), and 1.37 parts of dispersion resin (G-6) as dispersion resin (G) were mixed, and after shaking lightly by hand, the whole was stirred uniformly with a homodisper. In the quantum dot-containing composition (X-15) thus obtained, the ratio of the number of moles of (meth)acrylate groups in the multifunctional (meth)acrylate (A) to the number of moles of mercapto groups in the multifunctional thiol (B) was 0.43 / 0 (infinity due to division by zero).

[0160] <Experimental Example 16> As other compounds, 20 parts of triallyl isocyanurate (manufactured by Tokyo Chemical Industry Co., Ltd., allyl group amount 12.0 mmol / g), 25 parts of isobornyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd., (meth)acrylate group amount 4.50 mmol / g), 0.4 parts of green quantum dots and 0.07 parts of red quantum dots as quantum dots (D), 5 parts of Eposter MS (manufactured by Nippon Shokubai Co., Ltd., benzoguanamine-formaldehyde condensate particles) as scattering agent (E), 1 part of Irgacure TPO-L (manufactured by BASF) as photopolymerization initiator (F), and 54 parts of dispersion resin (G-3) as dispersion resin (G) were mixed and lightly shaken by hand, and then stirred with a homodisper until the whole was uniform. In the quantum dot-containing composition (X-16) thus obtained, the ratio of the number of moles of (meth)acrylate groups in the multifunctional (meth)acrylate (A) to the number of moles of mercapto groups in the multifunctional thiol (B) was 0 / 0 (infinity due to division by zero).

[0161] <Experimental Example 17> As the multifunctional (meth)acrylate (A), 60 parts of AD-TMP (manufactured by Shin-Nakamura Chemical Co., Ltd., ditrimethylolpropane tetraacrylate, (meth)acrylate group amount 8.51 mmol / g), as the multifunctional thiol (B), 40 parts of PEMP (manufactured by SC Organic Chemical Co., Ltd., pentaerythritol tetrakis (3-mercaptopropionate) mercapto group amount 8.19 mmol / g), as the quantum dots (D), 0.4 parts of green quantum dots, 0.07 parts of red quantum dots, 5 parts of Eposter MS (manufactured by Nippon Shokubai Co., Ltd., benzoguanamine-formaldehyde condensate particles) as the scattering agent (E), 0.4 parts of Irgacure 184 (manufactured by BASF) as the photopolymerization initiator (F), and 1.37 parts of dispersion resin (G-2) as the dispersion resin (G) were mixed, and after shaking lightly by hand, the whole was stirred uniformly with a homodisper. In the quantum dot-containing composition (X-17) thus obtained, the ratio of the number of moles of (meth)acrylate groups in the multifunctional (meth)acrylate (A) to the number of moles of mercapto groups in the multifunctional thiol (B) was 1.56.

[0162] <Experimental Example 18> As the multifunctional (meth)acrylate (A), 60 parts of AD-TMP (manufactured by Shin-Nakamura Chemical Co., Ltd., ditrimethylolpropane tetraacrylate, (meth)acrylate group amount 8.51 mmol / g), as the multifunctional thiol (B), 40 parts of PEMP (manufactured by SC Organic Chemical Co., Ltd., pentaerythritol tetrakis (3-mercaptopropionate), mercapto group amount 8.19 mmol / g), as the reaction retarder (C), 0.5 parts of triphenyl phosphite (manufactured by Tokyo Chemical Industry Co., Ltd.), as the quantum dot (D), 0.4 parts of green quantum dot, 0.07 parts of red quantum dot, 0.4 parts of Irgacure 184 (manufactured by BASF) as the photopolymerization initiator (F), 1.37 parts of dispersion resin (G-2) as the dispersion resin (G) were mixed, and after shaking lightly by hand, the whole was stirred with a homodisper until it became uniform. In the quantum dot-containing composition (X-18) thus obtained, the ratio of the number of moles of (meth)acrylate groups in the multifunctional (meth)acrylate (A) to the number of moles of mercapto groups in the multifunctional thiol (B) was 1.56.

[0163] <Experimental Example 19> As the multifunctional (meth)acrylate (A), 60 parts of AD-TMP (manufactured by Shin-Nakamura Chemical Co., Ltd., ditrimethylolpropane tetraacrylate, (meth)acrylate group amount 8.51 mmol / g) were used. As the multifunctional thiol (B), 40 parts of PEMP (manufactured by SC Organic Chemical Co., Ltd., pentaerythritol tetrakis(3-mercaptopropionate), mercapto group amount 8.19 mmol / g) were used. As the reaction retarder (C), tetraethyl 0.004 parts of ruthiuram disulfide (Tokyo Chemical Industry Co., Ltd.), 0.4 parts of green quantum dots as quantum dots (D), 0.07 parts of red quantum dots, 5 parts of Eposter MS (Nippon Shokubai Co., Ltd., benzoguanamine-formaldehyde condensate particles) as scattering agent (E), and 1.37 parts of dispersion resin (G-2) as dispersion resin (G) were mixed, and after shaking lightly by hand, the mixture was stirred with a homodisper until the whole was uniform. The ratio of the number of moles of (meth)acrylate groups of the multifunctional (meth)acrylate (A) to the number of moles of mercapto groups of the multifunctional thiol (B) in the quantum dot-containing composition (X-19) thus obtained was 1.56.

[0164] <Experimental Example 20> As the multifunctional (meth)acrylate (A), 35 parts of AD-TMP (manufactured by Shin-Nakamura Chemical Co., Ltd., ditrimethylolpropane tetraacrylate, (meth)acrylate group amount 8.51 mmol / g) were used. As the multifunctional thiol (B), 65 parts of PEMP (manufactured by SC Organic Chemical Co., Ltd., pentaerythritol tetrakis(3-mercaptopropionate), mercapto group amount 8.19 mmol / g) were used. As the reaction retarder (C), tetraethyl thiuram disulfide (manufactured by Tokyo Chemical Industry Co., Ltd., The mixture was mixed with 0.004 parts of 1,000g of 1,000g of 1,000g of 1,000g of 0 ...

[0165] <Experimental Example 21> As the multifunctional (meth)acrylate (A), 90 parts of AD-TMP (manufactured by Shin-Nakamura Chemical Co., Ltd., ditrimethylolpropane tetraacrylate, (meth)acrylate group amount 8.51 mmol / g) were used. As the multifunctional thiol (B), 10 parts of PEMP (manufactured by SC Organic Chemical Co., Ltd., pentaerythritol tetrakis(3-mercaptopropionate), mercapto group amount 8.19 mmol / g) were used. As the reaction retarder (C), tetraethyl thiuram disulfide (manufactured by Tokyo Chemical Industry Co., Ltd., The mixture was mixed with 0.004 parts of 1,000g of 1,000g of 1,000g of 1,000g of 0 ...

[0166] <Pot life evaluation of quantum dot-containing composition (X)> The viscosity of the obtained quantum dot-containing compositions (X-1) to (X-21) was measured immediately after preparation, and then the quantum dot-containing compositions were transferred to a sample tube with a lid and left to stand for 24 hours while stirring with a roller stirrer in a 25°C environment, and the viscosity of the quantum dot-containing composition was measured again. The viscosity immediately after preparation and the increase rate of the viscosity after 24 hours thus obtained were calculated from the following formula to evaluate the pot life of each quantum dot-containing composition. Viscosity increase rate (%) = (viscosity after 24 hours / viscosity immediately after preparation) x 100 Viscosity after 24 hours (cps) Viscosity immediately after creation (cps)

[0167] The evaluation criteria are as follows: ◎: Increase rate less than 120%. Good. 〇: Increase rate is 120% or more but less than 150%. Practical use is possible. △: Increase rate is 150% or more but less than 200%. Lower limit of practical use. ×: Increase rate of 200% or more or gelation occurred. Not practical.

[0168] [Table 2]

[0169] [Table 3]

[0170] The meanings of the abbreviations in Tables 2 and 3 are as follows: A-DCP: Shin-Nakamura Chemical Co., Ltd., A-DCP (dimethylol-tricyclodecane diacrylate) A-TMPT: A-TMPT (trimethylolpropane triacrylate), manufactured by Shin-Nakamura Chemical Co., Ltd. AD-TMP: AD-TMP (ditrimethylolpropane tetraacrylate), manufactured by Shin-Nakamura Chemical Co., Ltd. A-DPH: Shin-Nakamura Chemical Co., Ltd., A-DPH (dipentaerythritol hexaacrylate) UV-7650B: Manufactured by Nippon Gosei Kagaku Kogyo Co., Ltd., Shiko UV-7650B (urethane acrylate) EGMP-4: SC Organic Chemicals, EGMP-4 (Tetraethylene glycol bis(3-mercaptopropionate)) TMMP: SC Organic Chemicals, TMMP (trimethylolpropane tris(3-mercaptopropionate)) PEMP: PEMP (Pentaerythritol tetrakis(3-mercaptopropionate)) manufactured by SC Organic Chemicals MT PE1: Karenz MT PE1 (pentaerythritol tetrakis(3-mercaptobutyrate)) manufactured by Showa Denko DPMP: DPMP (dipentaerythritol hexakis (3-mercaptopropionate)) manufactured by SC Organic Chemicals D-918: D-918 (rutile-type titanium dioxide), manufactured by Sakai Chemical Industry Co., Ltd. MBX-5: Sekisui Chemical Co., Ltd., Techpolymer MBX-5 (cross-linked polymethyl methacrylate particles) MS: Nippon Shokubai Co., Ltd., Eposter MS (benzoguanamine-formaldehyde condensate particles) 2000M: Nissan Chemical Co., Ltd., Optobeads 2000M (melamine resin / silica composite particles) Irg184: BASF Irgacure 184 (alkylphenone photopolymerization initiator) TPO: BASF's Irgacure TPO (acylphosphine oxide photopolymerization initiator) TPO-L: BASF's Irgacure TPO-L (acylphosphine oxide photopolymerization initiator)

[0171] <Manufacturing of quantum dot-containing components> Using the quantum dot-containing compositions (X-1) to (X-21) of Experimental Examples 1 to 21, sheet members (Y-1) to (Y-21) having a laminated structure were obtained according to the method described below. Tables 4 and 5 show the properties of the quantum dot-containing compositions and sheet members used in the production and the results of the performance tests described below.

[0172] The quantum dot-containing compositions (X-1) to (X-21) were applied to the primer-treated surface of a 125 μm-thick PET film (one side of which was matte-treated and the other side was primer-treated, and the film had no barrier layer) using a roll coater so that the thickness of the cured film made of the quantum dot-containing composition was about 100 μm. A PET film of the same composition and thickness of 125 μm was then bonded to the primer-treated surface so that the ink was applied to the ink-coated surface. Then, the film was exposed to ultraviolet light (120 W / cm 2 A high-pressure mercury lamp was used, with an integrated light output of 1000 mJ / cm 2 A curing treatment was carried out by irradiating ultraviolet rays so that the curing reaction was completed. Thereafter, the sheet was left to stand at 40° C. for 12 hours to complete the curing reaction. In this manner, sheet members (Y-1) to (Y-21) having a thickness of about 350 μm were obtained.

[0173] (Performance test) <Evaluation of haze value and total light transmittance> The haze value and total light transmittance of the sheet members (Y-1) to (Y-21) were measured by the above-mentioned methods. <Evaluation of luminescence quantum yield of sheet material> The luminescence quantum yields of the sheet members (Y-1) to (Y-21) were measured by the above-mentioned method. The evaluation criteria are as follows. ◎: Quantum yield is 85% or more. Good. 〇: Quantum yield is 75% or more but less than 85%. Practical use is possible. △: Quantum yield is 65% or more but less than 75%, the lower limit of practical use. ×: Quantum yield is less than 65%. Not practical. <Evaluation of Adhesion> Using a 100 mm x 100 mm blade manufactured by Dumbbell Co., 10 pieces each of the sheet members (Y-1) to (Y-21) were punched out. The sheet members were visually evaluated for the presence or absence of lifting or peeling at the ends. The evaluation criteria are as follows. ◎: 0 pieces of lifting or peeling. Good. ○: 1 piece of lifting or peeling. Usable. △: 2 pieces of lifted or peeled off. Lower limit of practical use. ×: Three or more pieces of lifted or peeled off. Unacceptable. <Evaluation of durability over time> Each of the sheet members (Y-1) to (Y-21) was cut into three pieces measuring 50 mm x 50 mm, and stored for 1000 hours under the following three levels of conditions. The maintenance rates of the emission peak intensity of green light and red light before and after storage were calculated using the following formula. Retention rate of luminescence peak intensity (%) = (luminescence peak intensity after 1000 hours of storage / luminescence peak intensity before storage) x 100 The storage conditions over time are as follows. Condition 1: 60℃ 90%RH Blue LED on Condition 2: 65℃ 95%RH Blue LED not lit Condition 3: 85℃ Blue LED not lit The evaluation criteria for durability over time are shown below. ◎: Retention rate is 90% or more. Good. 〇: Maintenance rate is between 75% and 90%. Practical use possible △: Retention rate is between 60% and 75%. Lower limit of practical use ×: Maintenance rate is less than 60%. Not practical.

[0174] <Evaluation of edge discoloration of sheet material> In the evaluation of durability over time, the lengths of the discolored portions from the ends of the sheet members (Y-1) to (Y-21) stored for 1000 hours under condition 1 were measured using a digital microscope (Keyence Corporation, VHS-5000) at three points, and the discoloration was evaluated from the average length. The evaluation criteria are shown below. ◎: Discoloration area is less than 50 μm. Good. ○: Discolored area is 50 μm or more and less than 150 μm. Practical use is possible. △: Discolored area is 150 μm or more and less than 250 μm. Lower limit for practical use. ×: Discolored area is 250 μm or more. Not practical.

[0175] [Table 4]

[0176] [Table 5]

[0177] As shown in Tables 4 and 5, in Experimental Example 33, since polyfunctional thiol (B) was not used, the oxygen barrier of the cured film was insufficient, and the durability and edge discoloration resistance were significantly deteriorated.

[0178] In Experimental Example 34, since the multifunctional (meth)acrylate (A) was not used, the quantum dot-containing composition did not harden, and the adhesive strength and oxygen barrier properties were insufficient, resulting in significant deterioration in adhesion, durability, and edge discoloration.

[0179] In Experimental Example 35, a monofunctional (meth)acrylate was used instead of the multifunctional (meth)acrylate (A), so the crosslink density of the cured film was insufficient, sufficient oxygen barrier properties were not obtained, and durability and edge discoloration properties were significantly deteriorated.

[0180] In Experimental Example 36, a monofunctional thiol was used instead of the multifunctional thiol (B), so the crosslink density of the cured film was insufficient, sufficient oxygen barrier properties were not obtained, and durability and edge discoloration properties were significantly deteriorated.

[0181] In Experimental Example 37, a monofunctional (meth)acrylate and a low-reactivity polyfunctional arylate were used instead of the polyfunctional (meth)acrylate (A), and therefore a relatively good pot life was obtained even without using the reaction retarder (C). However, the degree of crosslinking of the cured film was insufficient, and sufficient oxygen barrier properties were not obtained, resulting in significant deterioration in durability and edge discoloration.

[0182] In Experimental Example 38, since the reaction retarder (C) was not used, after uniform stirring, a significant increase in viscosity occurred within about 10 minutes, and coating was not possible, so that it was not possible to evaluate the various performances of the laminate.

[0183] Experimental Example 39 is an example in which the scattering agent (E) was not used. Although the durability and edge discoloration were excellent, it was found that the wavelength of the excitation light was not converted by the quantum dots (D), making it difficult to select a sufficient optical path length.

[0184] Experimental Example 40 is an example in which the photopolymerization initiator (F) was not used. In this example, the crosslinking reaction hardly progressed due to ultraviolet irradiation, and delamination occurred, making it impossible to evaluate the various performances of the laminate. For this reason, it is necessary to use the photopolymerization initiator (F) or to use an additive to replace the photopolymerization initiator (F).

[0185] In Experimental Examples 41 and 42, the ratio of the number of moles of (meth)acrylate groups in the multifunctional (meth)acrylate to the number of moles of mercapto groups in the multifunctional thiol was either too small or too large, resulting in insufficient crosslink density, failure to obtain sufficient oxygen barrier properties, and a tendency toward deterioration in durability and edge discoloration.

[0186] On the other hand, Examples 22 to 32 are sheet members made using a quantum dot-containing composition containing a polyfunctional (meth)acrylate (A), a polyfunctional thiol (B), a reaction retarder (C), a scattering agent (D), a photopolymerization initiator (E), and a quantum dot emitter (F) in suitable ranges, and they had a good balance of haze value, total light transmittance, luminescence quantum yield of the laminate, adhesion, durability, and edge discoloration. Among the above experimental examples, experimental examples 29 to 32 showed excellent performance.

[0187] In Experimental Examples 29 to 32, the average number of functional groups per molecule of the multifunctional (meth)acrylate (A) and the multifunctional thiol (B) was within the suitable range of 2.5 or more, and therefore sufficient crosslinking density of the cured film was obtained, and excellent durability and edge discoloration resistance were obtained, compared to Experimental Example 1, which was outside the range. In Experimental Examples 29 to 32, the dispersing agent (G) was used, and therefore superior luminescence quantum yields were obtained as compared with Experimental Example 23, in which the dispersing agent (G) was not used.

[0188] In Experimental Examples 29 to 32, fine particles having a melamine and / or benzoguanamine structure were used as a scattering agent, and therefore superior luminescence quantum yields were obtained as compared with Experimental Examples 24 and 28, in which no scattering agent was used.

[0189] In Experimental Examples 29 to 32, the ratio of the number of moles of (meth)acrylate groups in the multifunctional (meth)acrylate to the number of moles of mercapto groups in the multifunctional thiol was in the more suitable range of 1.0 to 2.5, and therefore sufficient crosslinking density of the cured film was obtained, and excellent durability and edge discoloration resistance were obtained, compared with Experimental Examples 25 and 26, which were outside the range.

[0190] In Experimental Examples 29 to 32, the dispersant (G) used was at least one selected from acrylic resins, polyurethane resins, polyester resins, and polyethyleneimine resins, and therefore the compatibility with the quantum dots (D) was improved compared to Experimental Example 27, which used a thioether resin, and excellent luminescence quantum yield was obtained.

[0191] <Brightness experiment with and without partial reflective sheet> The following samples were used in the experiment: (Sample 1) Direct BL (blue light) + QD sheet + prism (Sample 2) Direct BL (blue light) + QD coated BLT sheet + prism (Sample 3) Direct BL (blue light) + BLT sheet + QD sheet + prism (Sample 4) Direct BL (blue light) + QD sheet + prism + DBEF (Sample 5) Direct BL (blue light) + QD coated BLT sheet + prism + DBEF (Sample 6) Direct BL (blue light) + BLT sheet + QD sheet + prism + DBEF

[0192] The BLT sheet is a partially reflective sheet manufactured by 3M. The QD sheet contains quantum dots that emit red and green light. The QD-coated BLT sheet is a BLT sheet with a QD layer formed by applying a QD liquid containing quantum dots that emit red and green light to the surface of the BLT sheet. DBEF is a reflective polarizing film (Dual Brightness Enhancement Film) manufactured by 3M.

[0193] In the experiment, the relationship between wavelength and luminance (emission intensity) was measured for each group of samples 1 to 3 and samples 4 to 6. The emission intensity was measured using a spectrofluorophotometer (FP-8500, manufactured by JASCO Corporation).

[0194] FIG. 16 is a graph showing the relationship between wavelengths of 400 nm to 700 nm and emission intensity for Samples 1 to 3. FIG. 17 is a graph showing the relationship between wavelengths of 400 nm to 700 nm and emission intensity for Samples 4 to 6. FIG. 18 is a graph showing the relationship between wavelengths of 500 nm to 700 nm and emission intensity for Samples 1 to 3. FIG. 19 is a graph showing the relationship between wavelengths of 500 nm to 700 nm and emission intensity for Samples 4 to 6. Note that in FIGS. 18 and 19, the range of emission intensity on the vertical axis is expanded compared to FIGS. 16 and 17.

[0195] 16 and 17, the blue light emission intensity was high in Samples 1 and 4, which did not have a partial reflecting sheet. In contrast, the blue light emission intensity was suppressed in Samples 2, 3, 5, and 6, which had a partial reflecting sheet.

[0196] Furthermore, as shown in Figures 18 and 19, in Samples 1 and 4, which do not have a partial reflective sheet, the red and green luminescence intensities were reduced, whereas in Samples 2, 3, 5, and 6, which have a partial reflective sheet, the red and green luminescence intensities were increased.

[0197] (Sample 7) Edge BL (blue light) + QD sheet + prism (Sample 8) Edge BL (blue light) + QD coated BLT sheet + prism (Sample 9) Edge BL (blue light) + BLT sheet + QD sheet + prism (Sample 10) Edge BL (blue light) + QD sheet + prism + DBEF (Sample 11) Direct BL (blue light) + QD coated BLT sheet + prism + DBEF (Sample 12)

[0198] Edge BL (blue light) + BLT sheet + QD sheet + prism + DBEF Samples 7 to 12 are experimental examples in which an edge BL is used instead of the direct-under BL of Samples 1 to 6. That is, Samples 1 to 6 have the direct-under type configuration shown in FIG. 10, and Samples 7 to 7 have the edge-under type configuration shown in FIG.

[0199] FIG. 20 is a graph showing the relationship between wavelengths of 400 nm to 700 nm and emission intensity for Samples 7 to 9. FIG. 21 is a graph showing the relationship between wavelengths of 400 nm to 700 nm and emission intensity for Samples 10 to 12. FIG. 22 is a graph showing the relationship between wavelengths of 500 nm to 700 nm and emission intensity for Samples 7 to 9. FIG. 23 is a graph showing the relationship between wavelengths of 500 nm to 700 nm and emission intensity for Samples 10 to 12. Note that in FIGS. 22 and 23, the range of emission intensity on the vertical axis is expanded compared to FIGS. 20 and 21.

[0200] As shown in Figures 20 and 22, samples 7 and 10, which do not have a partial reflective sheet, had high blue emission intensity, while samples 8, 9, 11, and 12, which had a partial reflective sheet, were able to suppress the blue emission intensity.

[0201] Furthermore, as shown in Figures 22 and 23, in samples 7 and 10, which do not have a partial reflective sheet, the red and green luminescence intensities were reduced, whereas in samples 8, 9, 11, and 12, which have a partial reflective sheet, the red and green luminescence intensities were increased.

[0202] As described above, it has been found that by using a partially reflective sheet, it is possible to increase the red and green emission intensities while suppressing the blue light emission intensity, thereby increasing the brightness of the white light emitted by wavelength-converting the light from the blue LED and suppressing brightness unevenness.

[0203] Furthermore, no significant difference was observed in the emission intensity between when QDs were applied to the surface of the BLT sheet and when the QD sheet was layered on top of the BLT sheet. [Industrial Applicability]

[0204] The present invention provides a quantum dot-containing composition that has an excellent pot life and can effectively suppress changes in luminescence intensity over time, and a quantum dot-containing member using the same. The quantum dot-containing member of the present invention can be used to realize backlight devices, light-guiding members, display devices, liquid crystal display elements, and the like that have stable wavelength conversion characteristics. [Explanation of symbols]

[0205] 1, 39: Quantum dot-containing materials 2: Base film 3: Quantum dot layer 5: Quantum dots 5a: Core section 5b: Shell part 6:Organic ligand 10a, 10b: resin film 20: Light emitting element 21: Composite quantum dot-containing material 22: Diffuser 30a: First roll of raw material 30b: Second roll of raw material 32: Winding roll 33, 34: Nip roll 35: Joint 36: Application means 37: Quantum dot-containing composition 38:Drying section 40: Light guide plate 41: Hardening reaction section 50:Display device 52:Support 54:Display section 55: Backlight device 60: Liquid crystal display element 61: Light guide plate 62, 64: Diffusion sheet 63: Prism sheet 65, 69: Polarizing plate 66, 68: Phase difference film 67: Liquid crystal cell

Claims

1. The composition includes a multifunctional (meth)acrylate, a multifunctional thiol, a reaction retarder, a quantum dot, a scattering agent, and a photopolymerization initiator, A quantum dot-containing composition, characterized in that the ratio of the number of moles of (meth)acrylate groups in the multifunctional (meth)acrylate to the number of moles of mercapto groups in the multifunctional thiol is in the range of 1.0 or more and 2.5 or less.

2. The composition includes a multifunctional (meth)acrylate, a multifunctional thiol, a reaction retarder, a quantum dot, a scattering agent, and a photopolymerization initiator, The quantum dot-containing composition is characterized in that the reaction retarder is contained in a range of 0.0005 mass% or more and 0.5 mass% or less with respect to 100 mass% of the sum of the multifunctional (meth)acrylate and the multifunctional thiol.

3. The quantum dot-containing composition according to claim 2, characterized in that the ratio of the number of moles of the (meth)acrylate group of the multifunctional (meth)acrylate to the number of moles of the mercapto group of the multifunctional thiol is in the range of 0.6 to 9.

0.

4. 3. The quantum dot-containing composition according to claim 1, wherein the reaction retarder is at least one selected from the group consisting of a phosphorous acid compound and a dithiocarbamate compound.

5. The quantum dot-containing composition according to claim 1, characterized in that the reaction retarder is contained in a range of 0.0005% by mass or more and 1% by mass or less, relative to 100% by mass of the sum of the multifunctional (meth)acrylate and the multifunctional thiol.

6. The quantum dot-containing composition according to claim 4 , wherein the reaction retarder comprises a dithiocarbamate compound.

7. 7. The quantum dot-containing composition according to claim 1, wherein the scattering agent contains fine particles having at least one of a melamine structure and a benzoguanamine structure.

8. Further comprising a dispersing resin, the dispersion resin is at least one selected from an acrylic resin, a polyurethane resin, a polyester resin, and a polyethyleneimine resin; 3. The quantum dot-containing composition according to claim 1, wherein the functional group of the dispersion resin is at least one selected from the group consisting of a phosphate group, an amino group, and a mercapto group.

9. The quantum dot-containing composition according to claim 8, characterized in that the dispersion resin is contained in a range of 0.1 mass% to 5 mass% with respect to a sum of the multifunctional (meth)acrylate and the multifunctional thiol being 100 mass%.

10. The quantum dot-containing composition according to claim 3, characterized in that the ratio of the number of moles of the (meth)acrylate group of the multifunctional (meth)acrylate to the number of moles of the mercapto group of the multifunctional thiol is in the range of 0.8 to 5.

5.

11. The quantum dot-containing composition according to claim 10, characterized in that the ratio of the number of moles of the (meth)acrylate group of the multifunctional (meth)acrylate to the number of moles of the mercapto group of the multifunctional thiol is in the range of 1.52 to 9.

0.

12. A quantum dot-containing member obtained by curing the quantum dot-containing composition according to any one of claims 1 to 11.

13. The quantum dot-containing member according to claim 12, characterized in that it comprises a quantum dot layer formed by curing the quantum dot-containing composition, and a base film covering at least one surface of the quantum dot layer.

14. The quantum dot-containing member according to claim 13, characterized in that it comprises a quantum dot layer obtained by curing the quantum dot-containing composition, a base film covering one side of the quantum dot layer, and an optical member in contact with the surface of the quantum dot layer opposite to the base film.

15. The quantum dot-containing member according to claim 14 , wherein the optical member is a light guide plate or a diffusion plate.

16. 16. The quantum dot-containing member according to claim 12, wherein a barrier layer is not disposed on a surface of the quantum dot-containing member.

17. A backlight device comprising the quantum dot-containing member according to any one of claims 12 to 16.

18. A display device comprising the quantum dot-containing member according to any one of claims 12 to 16.

19. A liquid crystal display element comprising a backlight device incorporating the quantum dot-containing member according to any one of claims 12 to 16.

Citation Information

Patent Citations

  • Storageestable photosensitive resin composition

    JP1979031727A

  • High-pressure hose

    JP1984040079A

  • Photopolymerizable composition

    JP1987081404A

  • quantum dot film

    JP2016511709A

  • Composition for forming cured film, cured film, light-emitting display element, film and method for forming cured film

    JP2017032918A